Adhesive composition, adhesive layer, and adhesive sheet

JP2023136273A5Pending Publication Date: 2025-03-11NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022041797
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-16
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing adhesive compositions used in display devices suffer from issues such as increased surface resistivity, corrosion of metal wiring, and defects like clouding or peeling due to the migration of antistatic agents, especially in moist heat environments, which affect the antistatic performance and transparency of adhesive layers.

Method used

A pressure-sensitive adhesive composition containing a block copolymer with a sea-island structure, comprising an adhesive segment and a conductive segment, which forms a continuous phase and a discontinuous phase, effectively reducing surface resistivity and enhancing antistatic properties by forming conductivity paths.

Benefits of technology

The adhesive composition achieves low surface resistivity and excellent antistatic performance, maintaining transparency and preventing defects like corrosion and migration of antistatic agents, even in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000047_0000
    Figure 00000047_0000
Patent Text Reader

Abstract

To provide an adhesive composition capable of forming an adhesive layer that exhibits low surface resistivity and has excellent antistatic performance.SOLUTION: An adhesive composition according to the present invention contains a block copolymer. The block copolymer includes an adhesive segment (A) and a conductive segment (B). The adhesive composition has a sea-island structure that has been phase-separated into a continuous phase and a non-continuous phase.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer, and a pressure-sensitive adhesive sheet, and more particularly to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer, and a pressure-sensitive adhesive sheet that are excellent in antistatic properties. [Background technology]

[0002] In recent years, display devices such as liquid crystal displays (LCDs) and input devices such as touch panels have been widely used in various fields. In the manufacture of these display devices and input devices, pressure-sensitive adhesive sheets are used to bond optical members. For example, transparent pressure-sensitive adhesive sheets are used to bond optical members in various display devices such as touch panels.

[0003] In the manufacture of these display devices and input devices, when the pressure-sensitive adhesive sheet is attached to the display device, the release liner protecting the pressure-sensitive adhesive layer is peeled off, which generates static electricity in the pressure-sensitive adhesive layer. The generated static electricity affects the alignment of the display cells of the display device and can cause display defects. As a means of suppressing the generation of such static electricity, an antistatic agent is blended into the pressure-sensitive adhesive layer to reduce its surface resistivity (e.g., Patent Documents 1 to 3).

[0004] In recent years, with the trend toward higher image quality, the effects of static electricity on display devices with high-density display cells have become greater. In order to efficiently remove static electricity, it is necessary to further reduce the surface resistivity of the adhesive sheet (for example, to 10 10 In addition, the demand for thinner and lighter display devices has led to a demand for thinner pressure-sensitive adhesive sheets, and in order to achieve thin pressure-sensitive adhesive sheets with low surface resistivity, it is necessary to incorporate a large amount of antistatic agent.

[0005] However, when a large amount of antistatic agent is incorporated into the pressure-sensitive adhesive layer, there is a problem that the antistatic agent precipitates on the surface of the pressure-sensitive adhesive layer, corroding metal wiring such as copper wiring. There is also a problem that the antistatic agent migrates from the pressure-sensitive adhesive layer to other optical components in a humid and hot environment, increasing the surface resistance value and reducing the antistatic properties. Furthermore, the compatibility between the pressure-sensitive adhesive layer and the antistatic agent decreases, resulting in poor transparency and appearance such as cloudiness, particularly in a humid and hot environment, and in some cases, foaming and peeling may occur.

[0006] As a means for solving the above-mentioned problems caused by blending an antistatic agent in a pressure-sensitive adhesive layer, a method of forming a pressure-sensitive adhesive layer from an antistatic pressure-sensitive adhesive composition containing a (meth)acrylic polymer containing a reactive ionic liquid as a monomer unit is known (e.g., Patent Documents 4 and 5). In the pressure-sensitive adhesive layer formed from this antistatic pressure-sensitive adhesive composition, the reactive ionic liquid is incorporated into the skeleton of the (meth)acrylic polymer, thereby suppressing concerns about bleed-out and said to have excellent low-fouling properties. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Publication No. 2020-187365 [Patent Document 2] Japanese Patent Application Publication No. 2019-56115 [Patent Document 3] WO2018 / 008712 publication [Patent Document 4] Japanese Patent Application Laid-Open No. 2014-141649 [Patent Document 5] Japanese Patent Application Laid-Open No. 2014-189787 Summary of the Invention [Problem to be solved by the invention]

[0008] In Patent Documents 4 and 5, the ionic components are uniformly dispersed in the adhesive layer, making it difficult to form paths for imparting conductivity, resulting in a problem of reduced antistatic properties.

[0009] Therefore, an object of the present invention is to provide a pressure-sensitive adhesive composition that can form a pressure-sensitive adhesive layer that exhibits low surface resistivity and has excellent antistatic properties. Another object of the present invention is to provide a pressure-sensitive adhesive layer that exhibits low surface resistivity and has excellent antistatic properties. Another object of the present invention is to provide a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer that exhibits low surface resistivity and has excellent antistatic properties. [Means for solving the problem]

[0010] Therefore, the present inventors conducted extensive research to solve the above-mentioned problems, and as a result, they found that in a pressure-sensitive adhesive composition containing a block copolymer including a pressure-sensitive adhesive segment and a conductive segment, and in which a sea-island structure is formed in which the layers are phase-separated into a continuous phase and a discontinuous phase, paths for imparting conductivity are efficiently formed, and a pressure-sensitive adhesive layer exhibiting low surface resistivity and excellent antistatic performance can be formed, thereby completing the present invention.

[0011] That is, a first aspect of the present invention provides a pressure-sensitive adhesive composition comprising a block copolymer, the block copolymer comprising an adhesive segment (A) and a conductive segment (B), and having a sea-island structure phase-separated into a continuous phase and a discontinuous phase. In this specification, the pressure-sensitive adhesive composition of the first aspect of the present invention may be referred to as the "pressure-sensitive adhesive composition of the present invention."

[0012] A second aspect of the present invention provides a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention. Herein, the pressure-sensitive adhesive layer of the second aspect of the present invention may be referred to as the "pressure-sensitive adhesive layer of the present invention." A third aspect of the present invention provides a pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer of the present invention. Herein, the pressure-sensitive adhesive sheet of the third aspect of the present invention may be referred to as the "pressure-sensitive adhesive sheet of the present invention." The pressure-sensitive adhesive layer of the present invention and the pressure-sensitive adhesive sheet of the present invention are formed from the pressure-sensitive adhesive composition of the present invention, and therefore exhibit low surface resistivity and excellent antistatic properties.

[0013] The pressure-sensitive adhesive composition of the present invention contains a block copolymer. In the pressure-sensitive adhesive composition of the present invention, this block copolymer is included as a base polymer constituting the pressure-sensitive adhesive composition of the present invention. In this specification, the block copolymer contained as a base polymer in the pressure-sensitive adhesive composition of the present invention may be referred to as the "block copolymer of the present invention."

[0014] In the pressure-sensitive adhesive composition of the present invention, the block copolymer of the present invention comprises an adhesive segment (A) and a conductive segment (B). In the block copolymer of the present invention, the adhesive segment (A) is a segment that imparts adhesiveness to the pressure-sensitive adhesive layer of the present invention. In addition, in the block copolymer of the present invention, the conductive segment (B) is a segment that imparts conductivity to the pressure-sensitive adhesive layer of the present invention and has an antistatic function.

[0015] The pressure-sensitive adhesive composition of the present invention has a sea-island structure in which the pressure-sensitive adhesive composition is phase-separated into a continuous phase and a discontinuous phase. The configuration in which the pressure-sensitive adhesive composition of the present invention has a sea-island structure is preferred in that paths for imparting conductivity are efficiently formed in the continuous phase, and the pressure-sensitive adhesive layer of the present invention exhibits low surface resistivity and excellent antistatic performance.

[0016] In the pressure-sensitive adhesive composition of the present invention, the continuous phase (sea portion) preferably contains the conductive segment (B). A configuration in which the continuous phase (sea portion) contains the conductive segment (B) is preferred in that paths for imparting conductivity are efficiently formed in the continuous phase, and the pressure-sensitive adhesive layer of the present invention exhibits low surface resistivity and excellent antistatic performance.

[0017] In the pressure-sensitive adhesive composition of the present invention, the weight ratio of the conductive segment (B) to the pressure-sensitive adhesive segment (A) (conductive segment (B) / pressure-sensitive adhesive segment (A)) is preferably 50 / 50 to 99 / 1. A weight ratio of 50 / 50 or more is preferable because it allows the pressure-sensitive adhesive composition of the present invention to form a sea-island structure in which the pressure-sensitive adhesive composition is phase-separated into a continuous phase and a discontinuous phase, and the continuous phase (sea portion) contains the conductive segment (B). It is also preferable because the sea-island structure forms nanometer-scale microphase separation. A weight ratio of 99 / 1 or less is preferable because it allows the pressure-sensitive adhesive layer of the present invention to have excellent adhesiveness.

[0018] In the pressure-sensitive adhesive composition of the present invention, the conductive segment (B) preferably contains, as a monomer unit, an ionic compound having a radically polymerizable substituent. The adhesive segment (A) preferably contains, as a monomer unit, a radically polymerizable compound. These configurations are preferred in that the block copolymer of the present invention can be efficiently prepared.

[0019] The pressure-sensitive adhesive layer of the present invention has a storage modulus of 3×10 at 25° C. and 1 Hz. 4 Pa or more 5×10 6 The pressure-sensitive adhesive layer of the present invention preferably has a storage modulus of 3×10 Pa or less at 25° C. and 1 Hz. 4 The storage modulus of the pressure-sensitive adhesive layer of the present invention at 25°C and 1 Hz is preferably 5 × 10 Pa or more from the viewpoint of the ability to conform to unevenness. 6 It is preferable that the pressure is 0.01 Pa or less.

[0020] The pressure-sensitive adhesive layer of the present invention preferably has a total light transmittance (based on JIS K7361-1) of 90% or more. The pressure-sensitive adhesive layer of the present invention preferably has a haze (based on JIS K7136) of 3% or less. These configurations are preferred in that excellent transparency and excellent appearance can be obtained.

[0021] The thickness of the pressure-sensitive adhesive sheet of the present invention is preferably 12 to 350 μm. A thickness of at least a certain level is preferred in that peeling at uneven areas is less likely to occur. A thickness of less than a certain level is also preferred in that an excellent appearance can be more easily maintained during production. [Effects of the Invention]

[0022] According to the pressure-sensitive adhesive composition of the present invention, a pressure-sensitive adhesive layer and a pressure-sensitive adhesive sheet exhibiting low surface resistivity and excellent antistatic properties can be obtained. [Brief explanation of the drawings]

[0023] [Figure 1] FIG. 1 is a schematic diagram (cross-sectional view) showing one embodiment of the pressure-sensitive adhesive sheet of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0024] The pressure-sensitive adhesive composition of the present invention contains a block copolymer, and the block copolymer contains an adhesive segment (A) and a conductive segment (B), and has a sea-island structure that is phase-separated into a continuous phase and a discontinuous phase.

[0025] The pressure-sensitive adhesive layer of the present invention is a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention. Furthermore, the pressure-sensitive adhesive sheet of the present invention is a pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer of the present invention.

[0026] [1. Pressure-sensitive adhesive composition] The pressure-sensitive adhesive composition of the present invention may have any form, such as a solvent-based, emulsion-based, hot-melt-based, or solventless-based (active energy ray-curable) composition. The pressure-sensitive adhesive composition of the present invention is particularly preferably a solvent-based one. A stable sea-island structure can be formed when a pressure-sensitive adhesive layer is obtained by heating and / or drying the solvent-based pressure-sensitive adhesive composition, which is preferred. In this specification, the pressure-sensitive adhesive composition refers to a composition used to form a pressure-sensitive adhesive layer, and includes the meaning of a composition used to form a pressure-sensitive adhesive.

[0027] The organic solvent is not particularly limited as long as it is an organic compound that can be used as a solvent, and examples thereof include hydrocarbon solvents such as cyclohexane, hexane, heptane, etc.; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, butanol, isopropyl alcohol, etc. The organic solvent may be a mixed solvent containing two or more organic solvents.

[0028] [1-1. Block copolymer of the present invention] The pressure-sensitive adhesive composition of the present invention contains a block copolymer. In the pressure-sensitive adhesive composition of the present invention, the block copolymer of the present invention is contained as a base polymer constituting the pressure-sensitive adhesive composition of the present invention.

[0029] The content (total amount) of the block copolymer of the present invention in the pressure-sensitive adhesive composition of the present invention is not particularly limited, but is preferably 75% by weight or more (e.g., 75 to 100% by weight), and more preferably 85% by weight or more (e.g., 85 to 99.99% by weight).

[0030] In the pressure-sensitive adhesive composition of the present invention, the block copolymer of the present invention comprises an adhesive segment (A) and a conductive segment (B). In the block copolymer of the present invention, the adhesive segment (A) is a segment that imparts adhesiveness to the pressure-sensitive adhesive layer of the present invention. In addition, in the block copolymer of the present invention, the conductive segment (B) is a segment that imparts conductivity to the pressure-sensitive adhesive layer of the present invention and has an antistatic function. The "segment" in the adhesive segment (A) and the conductive segment (B) refers to the partial structure that constitutes each block unit of the block copolymer.

[0031] The structure of the block copolymer of the present invention may be a linear block copolymer, a branched (star-shaped) block copolymer, or a mixture thereof. The structure of such a block copolymer may be appropriately selected depending on the desired physical properties of the block copolymer, but from the viewpoints of cost and ease of production, a linear block copolymer is preferred. Furthermore, the linear block copolymer may have any structure (arrangement), and (AB) n Type, (AB) n -A type (n is an integer of 1 or more, for example, an integer of 1 to 3). In these structures, A and B represent segments composed of different monomer compositions. In this specification, the segment represented by A constituting the linear block copolymer may be referred to as an "A segment," and the segment represented by B may be referred to as a "B segment."

[0032] Among these, from the viewpoint of ease of production, AB diblock copolymers represented by AB and ABA triblock copolymers represented by ABA are preferred, and ABA triblock copolymers are more preferred. It is believed that ABA triblock copolymers can exhibit a sea-island structure in which the A segments and B segments are microphase-separated on the nm scale due to pseudo-crosslinking between the A segments at both ends. In an ABA triblock copolymer, the two A segments located at both ends may be the same or different.

[0033] When the block copolymer of the present invention is an ABA triblock copolymer, at least one of the two A segments and one B segment (three in total) may be an adhesive segment (A) and at least one of the other segments may be a conductive segment (B). From the viewpoint of ease of production, an ABA triblock copolymer in which the A segment is the adhesive segment (A) and the B segment is the conductive segment (B) is preferred. In this case, an ABA triblock copolymer in which at least one of the two A segments is an adhesive segment (A) and the B segment is a conductive segment (B) is preferred, and an ABA triblock copolymer in which both of the two A segments are adhesive segments (A) and the B segment is a conductive segment (B) is more preferred.

[0034] The block copolymer of the present invention is composed of a plurality of segments (including an adhesive segment (A) and a conductive segment (B)) obtained by polymerizing monomer components. From the viewpoint of ease of preparation of the block copolymer, it is preferable that the monomer components include a radically polymerizable compound (a compound having a radically polymerizable substituent).

[0035] The radically polymerizable substituent in the radically polymerizable compound is not particularly limited, and examples thereof include a (meth)acryloyloxy group, a (meth)acryloylamino group, a vinyl group, an allyl group, a styryl group, etc. Among these, a (meth)acryloyloxy group and a (meth)acryloylamino group are preferred, and from the viewpoint of ease of preparation of a block copolymer, a monomer having a (meth)acryloyloxy group as a radically polymerizable substituent (a (meth)acrylic monomer) is particularly preferred.

[0036] Note that "(meth)acrylic" means "acrylic" and / or "methacrylic" (either or both of "acrylic" and "methacrylic"), and the same applies hereinafter. Furthermore, "(meth)acryloyl group" means "acryloyl group" and / or "methacryloyl group" (either or both of "acryloyl group" and "methacryloyl group"), and the same applies hereinafter.

[0037] The block copolymer of the present invention or each segment thereof (including the adhesive segment (A) and the conductive segment (B)) preferably contains 70% by weight or more, more preferably 80% by weight or more, and particularly preferably 90% by weight or more of a (meth)acrylic monomer relative to the total amount of the monomer components (100% by weight).

[0038] The block copolymer of the present invention or each segment thereof (including the adhesive segment (A) and the conductive segment (B)) preferably contains, as a main monomer unit, a monomer component derived from a (meth)acrylic acid alkyl ester having a linear or branched alkyl group (hereinafter, sometimes simply referred to as "(meth)acrylic acid alkyl ester") as an essential monomer unit.

[0039] Examples of the (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate), isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, Examples of the alkyl (meth)acrylate include nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. These alkyl (meth)acrylates may be used alone or in combination of two or more.

[0040] Among these, the (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 18 carbon atoms, from the viewpoint of obtaining strong adhesion and adjusting residual stress, and more preferably methyl methacrylate (MMA), butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), or isostearyl acrylate (ISTA).

[0041] The content (ratio) of the (meth)acrylic acid alkyl ester in all monomer units of the block copolymer of the present invention (total amount of monomer components constituting the block copolymer) is not particularly limited, but from the viewpoint of adhesive reliability, it is preferably 1 to 50 parts by weight, more preferably 3 to 40 parts by weight, and even more preferably 5 to 30 parts by weight, relative to the total amount (100 parts by weight) of the monomer components constituting the block copolymer of the present invention.

[0042] It is also preferable that the block copolymer of the present invention or each segment thereof (including the adhesive segment (A) and the conductive segment (B)) contains, as an essential monomer unit, a (meth)acrylic acid alkoxyalkyl ester having a linear or branched alkoxyalkyl group (hereinafter, sometimes simply referred to as "(meth)acrylic acid alkoxyalkyl ester").

[0043] Examples of the alkoxyalkyl (meth)acrylate include alkyl (meth)acrylates having an alkoxyalkyl group in which an alkoxy group having 1 to 20 carbon atoms is substituted on an alkyl group having 1 to 20 carbon atoms, such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. The alkyl (meth)alkoxyacrylates may be used alone or in combination of two or more.

[0044] Among these, the (meth)acrylic acid alkoxyalkyl ester is preferably a (meth)acrylic acid alkoxyalkyl ester in which an alkoxy group having 1 to 18 carbon atoms is substituted with an alkyl group having 1 to 18 carbon atoms, from the viewpoint of obtaining strong adhesion and adjusting residual stress, and more preferably 2-methoxyethyl acrylate (MEA).

[0045] The content (ratio) of the (meth)acrylic acid alkoxyalkyl ester in all monomer units of the block copolymer of the present invention (total amount of monomer components constituting the block copolymer) is not particularly limited, but from the viewpoint of adhesive reliability, it is preferably 30 to 99 parts by weight, more preferably 40 to 95 parts by weight, and even more preferably 50 to 90 parts by weight, relative to the total amount (100 parts by weight) of the monomer components constituting the block copolymer of the present invention.

[0046] The block copolymer of the present invention may contain, as a monomer unit, a copolymerizable monomer (copolymerizable monomer) in addition to the (meth)acrylic acid alkyl ester and (meth)acrylic acid alkoxyalkyl ester. That is, the block copolymer of the present invention may contain a copolymerizable monomer as a constituent monomer component. The copolymerizable monomer may be used alone or in combination of two or more kinds.

[0047] The copolymerizable monomer is preferably a carboxyl group-containing monomer. When the block copolymer of the present invention contains a carboxyl group-containing monomer as a monomer unit, it is easy to obtain good cohesive strength. Therefore, it is easy to obtain strong adhesiveness. Furthermore, the carboxyl group can also serve as a reaction site with the crosslinking agent described below.

[0048] The content (ratio) of the carboxyl group-containing monomer relative to the total amount (100 parts by weight) of the monomer components constituting the block copolymer of the present invention is not particularly limited. The content of the carboxyl group-containing monomer is preferably 0.1 to 20 parts by weight, more preferably 0.3 to 10 parts by weight, and even more preferably 0.5 to 5 parts by weight, in terms of cohesive strength, adhesiveness, ease of obtaining adhesive reliability, and reactivity with a crosslinking agent.

[0049] Preferred examples of the copolymerizable monomer include hydroxyl group-containing monomers. When the block copolymer of the present invention contains a hydroxyl group-containing monomer as a monomer unit, the constituent monomer components are easily polymerized, and good cohesive strength is easily obtained. This makes it easier to obtain strong adhesion, and also makes it easier to increase the gel fraction and obtain excellent anti-foaming and peeling properties. Furthermore, it makes it easier to suppress whitening of the PSA sheet, which can occur in high-humidity environments. Furthermore, the hydroxyl group can also serve as a reaction site with the crosslinking agent described below.

[0050] The content (ratio) of the hydroxyl group-containing monomer relative to the total amount (100 parts by weight) of the monomer components constituting the block copolymer of the present invention is not particularly limited. When the amount of the hydroxyl group-containing monomer is at least a certain level, whitening of the PSA sheet, which may occur in a high-humidity environment, can be further suppressed, and transparency such as resistance to humidification can be ensured. The lower limit of the content of the hydroxyl group-containing monomer is preferably at least 1 part by weight, more preferably at least 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, and even more preferably at least 10 parts by weight. Furthermore, in terms of cohesive strength, adhesiveness, foam-peeling resistance, and other adhesive reliability, the upper limit of the content of the hydroxyl group-containing monomer is preferably at most 40 parts by weight, more preferably at most 35 parts by weight, 34 parts by weight, 33 parts by weight, 32 parts by weight, or 31 parts by weight, and even more preferably at most 30 parts by weight.

[0051] Furthermore, nitrogen-containing monomers are preferred as the copolymerizable monomer. When the block copolymer of the present invention contains a nitrogen-containing monomer as a monomer unit, it is easier to obtain a moderate cohesive strength. This increases the 180° peel adhesive strength to a glass plate and the 180° peel adhesive strength to an acrylic plate, making it easier to obtain strong adhesion, and also increases the gel fraction, making it easier to obtain excellent foam-peel resistance. Furthermore, it is easier to obtain moderate flexibility in the pressure-sensitive adhesive layer, and it is easier to adjust the 300% tensile residual stress within a specific range, making it easier to obtain excellent stress relaxation properties and excellent step-conforming properties.

[0052] The content (ratio) of the nitrogen-atom-containing monomer relative to the total amount (100 parts by weight) of the monomer components constituting the block copolymer of the present invention is not particularly limited, but is preferably 0.1 parts by weight or more. The lower limit of the content of the nitrogen-atom-containing monomer relative to the total amount (100 parts by weight) of the monomer components constituting the block copolymer of the present invention is preferably 0.5 parts by weight or more, more preferably 0.8 parts by weight or more, and even more preferably 1 part by weight or more, from the viewpoints of cohesive strength, adhesiveness, and foam-peel resistance. The upper limit of the content of the nitrogen-atom-containing monomer is preferably 10 parts by weight or less, more preferably 8 parts by weight or less, and even more preferably 5 parts by weight or less, from the viewpoints of more easily achieving appropriate flexibility in the pressure-sensitive adhesive layer and more easily achieving excellent stress relaxation properties and excellent step-following properties.

[0053] [1-2. Carboxyl group-containing monomers] It is preferable that the monomer component constituting the block copolymer of the present invention contains a carboxyl group-containing monomer. By containing a carboxyl group-containing monomer as a monomer component constituting the block copolymer of the present invention, it is preferable that the monomer component serves as a reaction site with the crosslinking agent described below, forming a crosslinked structure and efficiently forming the sea-island structure described below. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid. The carboxyl group-containing monomer also includes acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride. The carboxyl group-containing monomers may be used alone or in combination of two or more.

[0054] [1-3. Hydroxyl group-containing monomers] A hydroxyl group-containing monomer refers to a monomer having at least one hydroxyl group in the molecule. A monomer having at least one hydroxyl group and at least one carboxyl group in the molecule is a carboxyl group-containing monomer, but not a hydroxyl group-containing monomer. The hydroxyl group-containing monomer is not particularly limited, but specific examples include hydroxyl group-containing (meth)acrylic acid esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and 4-hydroxymethylcyclohexyl (meth)acrylate; vinyl alcohol; and allyl alcohol. Among these, the hydroxyl group-containing monomer is preferably a hydroxyl group-containing (meth)acrylic acid ester, more preferably 2-hydroxyethyl acrylate (HEA), 2-hydroxypropyl (meth)acrylate (HPA), or 4-hydroxybutyl acrylate (4HBA). The hydroxyl group-containing monomer may be used alone or in combination of two or more kinds.

[0055] [1-4. Nitrogen-containing monomers] A nitrogen atom-containing monomer refers to a monomer having at least one nitrogen atom in the molecule (per molecule). However, the hydroxyl group-containing monomer does not include the nitrogen atom-containing monomer. In other words, in this specification, a monomer having a hydroxyl group and a nitrogen atom in the molecule is included in the nitrogen atom-containing monomer. Furthermore, a monomer having at least one nitrogen atom in the molecule and at least one carboxyl group in the molecule is a carboxyl group-containing monomer, but is not a nitrogen atom-containing monomer.

[0056] From the viewpoint of improving resistance to foaming and peeling, the nitrogen atom-containing monomer is preferably an N-vinyl cyclic amide, a (meth)acrylamide, a heterocycle-containing monomer, etc. The nitrogen atom-containing monomer may be used alone or in combination of two or more kinds.

[0057] Examples of the heterocycle-containing monomer include (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyloxazole, vinylisoxazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, and N-methylvinylpyrrolidone.

[0058] The N-vinyl cyclic amides include N-vinyl cyclic amides represented by the following formula (1). [ka] (In formula (1), R 1 indicates a divalent organic group)

[0059] R in the above formula (1) 1 is a divalent organic group, preferably a divalent saturated or unsaturated hydrocarbon group, and more preferably a divalent saturated hydrocarbon group (for example, an alkylene group having 3 to 5 carbon atoms).

[0060] As the N-vinyl cyclic amide represented by the above formula (1), from the viewpoint of further improving foaming and peeling resistance, N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, etc. are preferred, more preferably N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam, and even more preferably N-vinyl-2-pyrrolidone.

[0061] Examples of the (meth)acrylamides include (meth)acrylamide, N-alkyl(meth)acrylamide, and N,N-dialkyl(meth)acrylamide. Examples of the N-alkyl(meth)acrylamide include N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, and N-octylacrylamide. Furthermore, the N-alkyl(meth)acrylamides also include (meth)acrylamides having an amino group, such as dimethylaminoethyl(meth)acrylamide, diethylaminoethyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide. Examples of the N,N-dialkyl(meth)acrylamide include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide.

[0062] The (meth)acrylamides also include, for example, various N-hydroxyalkyl(meth)acrylamides. Examples of the N-hydroxyalkyl(meth)acrylamides include N-methylol(meth)acrylamide, N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(2-hydroxybutyl)(meth)acrylamide, N-(3-hydroxybutyl)(meth)acrylamide, N-(4-hydroxybutyl)(meth)acrylamide, and N-methyl-N-2-hydroxyethyl(meth)acrylamide.

[0063] The (meth)acrylamides also include, for example, various N-alkoxyalkyl(meth)acrylamides, such as N-methoxymethyl(meth)acrylamide and N-butoxymethyl(meth)acrylamide.

[0064] Furthermore, examples of nitrogen atom-containing monomers other than the heterocycle-containing monomers, N-vinyl cyclic amides, and (meth)acrylamides include amino group-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; maleimide-based monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; N-methylitaconimide, N-ethyl Examples of the monomer include itaconimide-based monomers such as itaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-laurylitaconimide, and N-cyclohexylitaconimide; imide group-containing monomers such as succinimide-based monomers such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyoctamethylene succinimide; and isocyanate group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate.

[0065] [1-5. Alicyclic structure-containing monomers] Copolymerizable monomers other than carboxyl group-containing monomers, nitrogen atom-containing monomers, and hydroxyl group-containing monomers may further include alicyclic structure-containing monomers. The alicyclic structure-containing monomers are not particularly limited as long as they have a polymerizable functional group with an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group, and an alicyclic structure. For example, alkyl (meth)acrylates having a cycloalkyl group are included in the alicyclic structure-containing monomers. The alicyclic structure-containing monomers may be used alone or in combination of two or more.

[0066] The alicyclic structure in the alicyclic structure-containing monomer is a cyclic hydrocarbon structure, preferably having 5 or more carbon atoms, more preferably 6 to 24 carbon atoms, still more preferably 6 to 15 carbon atoms, and particularly preferably 6 to 10 carbon atoms.

[0067] Examples of the alicyclic structure-containing monomer include cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, HPMPA represented by the following formula (2), TMA-2 represented by the following formula (3), and HCPA represented by the following formula (4). In the following formula (4), the bonding position between the cyclohexyl ring connected by a line and the structural formula in parentheses is not particularly limited. Among these, isobornyl (meth)acrylate is preferred. [ka] [ka] [ka]

[0068] When the block copolymer of the present invention contains the above-mentioned alicyclic structure-containing monomer as a monomer component constituting the polymer, the proportion of the above-mentioned alicyclic structure-containing monomer in the total monomer components (100% by weight) constituting the block copolymer of the present invention is not particularly limited, but is preferably 10% by weight or more in terms of improving durability and obtaining high adhesive reliability. Furthermore, the upper limit of the proportion of the above-mentioned alicyclic structure-containing monomer is preferably 50% by weight or less, more preferably 40% by weight or less, and even more preferably 30% by weight or less in terms of obtaining a pressure-sensitive adhesive layer with appropriate flexibility.

[0069] [1-6. Other copolymerizable monomers] Examples of copolymerizable monomers in the block copolymer of the present invention include, in addition to the above-mentioned carboxyl group-containing monomers, nitrogen atom-containing monomers, and hydroxyl group-containing monomers, epoxy group-containing monomers [e.g., glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, etc.]; sulfonic acid group-containing monomers [e.g., sodium vinyl sulfonate, etc.]; phosphate group-containing monomers; (meth)acrylic acid esters having aromatic hydrocarbon groups [e.g., phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, etc.]; vinyl esters [e.g., vinyl acetate, vinyl propionate, etc.]; aromatic vinyl compounds [e.g., styrene, vinyl toluene, etc.]; olefins or dienes [e.g., ethylene, propylene, butadiene, isoprene, isobutylene, etc.]; vinyl ethers [e.g., vinyl alkyl ether, etc.]; and vinyl chloride.

[0070] Furthermore, the copolymerizable monomer in the block copolymer of the present invention may also be a polyfunctional monomer. The polyfunctional monomer acts as a cross-linking component. Examples of the polyfunctional monomer include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. The polyfunctional monomer may be used alone or in combination of two or more.

[0071] The content (proportion) of the polyfunctional monomer in all monomer units of the block copolymer of the present invention is not particularly limited, but is preferably 0.5 parts by weight or less (e.g., 0 to 0.5 parts by weight), more preferably 0 to 0.35 parts by weight, and even more preferably 0 to 0.3 parts by weight, relative to the total amount (100 parts by weight) of the monomer components constituting the block copolymer of the present invention. A polyfunctional monomer content of 0.5 parts by weight or less is preferred because the pressure-sensitive adhesive layer has adequate cohesive strength, and adhesive strength and level difference absorbency are likely to be improved. When a crosslinking agent is used, the polyfunctional monomer does not need to be used; however, when a crosslinking agent is not used, the polyfunctional monomer content is preferably 0.001 to 0.5 parts by weight, more preferably 0.001 to 0.35 parts by weight, and even more preferably 0.002 to 0.3 parts by weight.

[0072] [1-7. Adhesive segment (A)] In the block copolymer of the present invention, the adhesive segment (A) is a segment that imparts adhesiveness to the adhesive layer of the present invention. The monomer component constituting the adhesive segment (A) is preferably the above-mentioned radically polymerizable compound.

[0073] The monomer components constituting the adhesive segment (A) preferably contain the above-mentioned (meth)acrylic acid alkyl ester and nitrogen atom-containing monomer as essential monomers from the viewpoints of cohesive strength, adhesiveness, and resistance to foaming and peeling. As the nitrogen atom-containing monomer, from the viewpoints of cohesive strength, adhesiveness, and resistance to foaming and peeling, a heterocycle-containing monomer is preferred, and (meth)acryloylmorpholine is more preferred.

[0074] The content (ratio) of the (meth)acrylic acid alkyl ester in all monomer units of the adhesive segment (A) (total amount of monomer components constituting the adhesive segment (A)) is not particularly limited, but from the viewpoint of adhesive reliability, it is preferably 30 to 95 parts by weight, more preferably 35 to 90 parts by weight, and even more preferably 40 to 85 parts by weight, relative to the total amount (100 parts by weight) of monomer components constituting the adhesive segment (A).

[0075] The content (ratio) of the nitrogen atom-containing monomer (particularly, heterocycle-containing monomer) in all monomer units of the adhesive segment (A) (total amount of monomer components constituting the adhesive segment (A)) is not particularly limited, but from the viewpoints of cohesive strength, adhesiveness, and foaming and peeling resistance, it is preferably 5 to 40 parts by weight, more preferably 7 to 35 parts by weight, and even more preferably 10 to 30 parts by weight, relative to the total amount (100 parts by weight) of monomer components constituting the block copolymer of the present invention.

[0076] It is also preferred that the monomer component constituting the adhesive segment (A) contains a carboxyl group-containing monomer, which serves as a reaction site with the crosslinking agent described below to form a crosslinked structure and efficiently form the sea-island structure described below.

[0077] The content (ratio) of the carboxyl group-containing monomer relative to the total amount (100 parts by weight) of the monomer components constituting the adhesive segment (A) is not particularly limited, but from the standpoints of cohesive strength, adhesiveness, ease of obtaining adhesive reliability, and reactivity with the crosslinking agent, it is preferably 1 to 20 parts by weight, more preferably 2 to 15 parts by weight, and even more preferably 3 to 10 parts by weight.

[0078] [1-8. Conductive Segment (B)] In the block copolymer of the present invention, the conductive segment (B) is a segment that imparts conductivity to the pressure-sensitive adhesive layer of the present invention and has an antistatic function. The monomer component constituting the conductive segment (B) is preferably the above-mentioned radically polymerizable compound.

[0079] The monomer component constituting the conductive segment (B) preferably contains the above-mentioned (meth)acrylic acid alkoxyalkyl ester as an essential monomer unit, from the viewpoint of making it easier to impart conductivity.

[0080] The content (ratio) of the (meth)acrylic acid alkoxyalkyl ester in all monomer units of the conductive segment (B) (total amount of monomer components constituting the conductive segment (B)) is not particularly limited, but from the viewpoint of efficiently forming a sea-island structure, it is preferably 50 to 99 parts by weight, more preferably 70 to 98 parts by weight, and even more preferably 80 to 95 parts by weight relative to the total amount (100 parts by weight) of monomer components constituting the conductive segment (B).

[0081] The monomer components constituting the conductive segment (B) preferably include, in addition to the above-mentioned radically polymerizable compound, an ionic compound having a radically polymerizable substituent (hereinafter sometimes referred to as an "ionic monomer" in this specification). The ionic monomer is a monomer component that imparts conductivity and antistatic properties to the conductive segment (B).

[0082] The ionic monomer is a monomer component having a radical polymerizable substituent in the cation moiety and / or the anion moiety (either or both) constituting the ionic monomer. The ionic monomer is preferably a liquid (liquid state) anywhere within the range of 0 to 150°C, a non-volatile molten salt, and transparent (ionic liquid). The ionic monomer may be used alone or in combination of two or more kinds.

[0083] When the conductive segment (B) contains an ionic monomer as a monomer component, the ionic monomer is incorporated into the molecule of the conductive segment (B), thereby maintaining compatibility in the pressure-sensitive adhesive layer of the present invention and making it easier to maintain transparency. Furthermore, bleed-out of the antistatic component can be suppressed even under harsh conditions such as humid and hot environments, making it less likely to cause defects such as corrosion of metal wiring. Furthermore, an increase in surface resistance in humid and hot environments can be suppressed, making it possible to maintain excellent antistatic properties. Furthermore, precipitation, foaming, and peeling on the surface of the pressure-sensitive adhesive layer are suppressed, making it less likely to cause poor durability, such as poor appearance and adhesion reliability. Therefore, a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention containing the block copolymer of the present invention containing the conductive segment (B) is useful because it satisfies excellent antistatic properties, transparency, humid and heat resistance, and low contamination.

[0084] The cation moiety of the ionic monomer can be any cation that can be used without particular limitation, and examples thereof include a quaternary ammonium cation, an imidazolium cation, a pyridinium cation, a piperidinium cation, a pyrrolidinium cation, a quaternary phosphonium cation, a trialkylsulfonium cation, a pyrrole cation, a pyrazolium cation, and a guanidium cation. Among these, it is more preferable to use a quaternary ammonium cation, an imidazolium cation, a pyridinium cation, a piperidinium cation, a pyrrolidinium cation, a quaternary phosphonium cation, or a trialkylsulfonium cation.

[0085] In addition, among the anion moieties constituting the ionic monomer, the anion is SCN- , BF4 - , PF6 - , NO3 - , CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (FSO2)2N - , (CF3SO2)2N - , (CF3SO2) 3 C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , F(HF) n - , (CN)2N - , C4F9SO3 - , (C2F5SO2)2N - , C3F7COO - , (CF3SO2)(CF3CO)N - , B(CN)4 - , C(CN)3 - , N(CN)2 - , CH3OSO3 - , C2H5OSO3 - , C4H9OSO3 - , C6H 13 OSO3 - , C8H 17 OSO3 - , p-toluenesulfonate anion, 2-(2-methoxyethyl)ethyl sulfate anion, (C2F5)3PF3 - In particular, an anion component containing a fluorine atom (fluorine-containing anion) is preferred because it can produce an ionic compound with a low melting point and has excellent antistatic properties. Note that it is preferable not to use chloride ions, bromide ions, etc. as anions because they are corrosive.

[0086] Examples of the radical polymerizable substituent possessed by the ionic monomer include a (meth)acryloyloxy group, a (meth)acryloylamino group, a vinyl group, an allyl group, a styryl group, etc. Among these, a (meth)acryloyloxy group and a (meth)acryloylamino group are preferred, and a (meth)acryloyloxy group is particularly preferred.

[0087] The number of radical polymerizable substituents possessed by the ionic monomer is not particularly limited, but is preferably 1 to 4, more preferably 1 to 3, even more preferably 1 or 2, and particularly preferably 1. When the number of radical polymerizable substituents is 2 or more, the 2 or more radical polymerizable substituents may be the same or different. Note that when the number of radical polymerizable substituents is 2 or more, the ionic monomer may also function as a crosslinking agent that crosslinks two or more polymers.

[0088] The ionic monomer can be used without any particular limitation, but is preferably an ionic compound represented by the following general formula (A). [ka]

[0089] In the above general formula (A), X + is the cation part. Y - is an anion. Z 1 and Z 2 are the same or different and each represents a single bond or an alkylene group having 1 to 16 carbon atoms. 1 and A 2 are the same or different and are radically polymerizable substituents. 1 is 0 or 1, n 2 is 0 or 1, where n 1 +n 2 is 1 or 2.

[0090] The cationic moiety (X +) include quaternary ammonium groups, imidazolium groups, pyridinium groups, piperidinium groups, pyrrolidinium groups, pyrrolidinium groups, pyrrole groups, quaternary phosphonium groups, trialkylsulfonium groups, pyrazolium groups, and guanidium groups. Among these, quaternary ammonium groups are particularly preferred because of their excellent transparency and electronic and optical applications. Furthermore, quaternary ammonium groups are preferred because they are unlikely to inhibit general radical polymerization reactions during ultraviolet (UV) curing and are thought to have high curability.

[0091] The quaternary ammonium group may be n 1 +n 2 When is 1, examples of the alkyl group include a trimethylammonium group, a triethylammonium group, a tripropylammonium group, a methyldiethylammonium group, an ethyldimethylammonium group, a methyldipropylammonium group, a dimethylbenzylammonium group, a diethylbenzylammonium group, a methyldibenzylammonium group, an ethyldibenzylammonium group, a dimethyloctadecylammonium group, and a dimethyloleylammonium group. Among these, a trimethylammonium group and a dimethylbenzylammonium group are particularly preferred in that they are inexpensive industrial materials that are easily available.

[0092] The quaternary ammonium group may be n 1 +n 2 When is 2, examples of the alkyl group include a dimethylammonium group, a diethylammonium group, a dipropylammonium group, a methylethylammonium group, a methylpropylammonium group, a methylbenzylammonium group, an ethylbenzylammonium group, a methyloctadecylammonium group, an ethyloctadecylammonium group, a methyloleylammonium group, and an ethyloleylammonium group. Among these, a dimethylammonium group and a methyloleylammonium group are particularly preferred in that they are inexpensive industrial materials that are easily available.

[0093] The anion (site) (Y - ) in which the anion is SCN- , BF4 - , PF6 - , NO3 - , CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (FSO2)2N - , (CF3SO2)2N - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , F(HF) n - , (CN)2N - , C4F9SO3 - , (C2F5SO2)2N - , C3F7COO - , (CF3SO2)(CF3CO)N - , B(CN)4 - , C(CN)3 - , N(CN)2 - , CH3OSO3 - , C2H5OSO3 - , C4H9OSO3 - , C6H 13 OSO3 - , C8H 17 OSO3 - , p-toluenesulfonate anion, 2-(2-methoxyethyl)ethyl sulfate anion, (C2F5)3PF3 - In particular, an anion component containing a fluorine atom (fluorine-containing anion) is preferred because it can produce an ionic compound with a low melting point and has excellent antistatic properties. Note that it is preferable not to use chloride ions, bromide ions, etc. as anions because they are corrosive.

[0094] Z constituting the ionic monomer represented by the general formula (A) 1 and Z 2is a single bond or an alkylene group having 1 to 16 carbon atoms. The alkylene group having 1 to 16 carbon atoms is preferably an alkylene group having 1 to 12 carbon atoms, more preferably an alkylene group having 1 to 6 carbon atoms, and particularly preferably an alkylene group having 1 to 3 carbon atoms. Specific examples include a methylene group, an ethylene group, a trimethylene group, and a methylethylene group, with an ethylene group and a trimethylene group being preferred. 1 +n 2 If is 2, Z 1 and Z 2 may be the same or different.

[0095] A constituting the ionic monomer represented by the above general formula (A) 1 and A 2 is a radically polymerizable substituent, and specific examples thereof include a (meth)acryloyloxy group, a (meth)acryloylamino group, a vinyl group, an allyl group, and a styryl group. Among these, a (meth)acryloyloxy group and a (meth)acryloylamino group are preferred, and a (meth)acryloyloxy group that can be copolymerized with the radically polymerizable compound is particularly preferred. 1 +n 2 If is 2, A 1 and A 2 may be the same or different.

[0096] Among the ionic monomers represented by the general formula (A), X + is a quaternary ammonium group, and n 1 is 1 and n 2 is 0 and A 1Specific examples of the embodiment in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include N,N,N-trialkyl-N-vinylammonium tetrafluoroborate, N,N,N-trialkyl-N-vinylammonium trifluoroacetate, N,N,N-trialkyl-N-vinylammonium heptafluorobutyrate, N,N,N-trialkyl-N-vinylammonium trifluoromethanesulfonate, N,N,N-trialkyl-N-vinylammonium perfluorobutanesulfonate, N,N,N-trialkyl-N-vinylammonium bis(trifluoromethanesulfonyl)imide, N Ionic compounds containing N,N,N-trialkyl-N-vinylammonium cations, such as N,N-trialkyl-N-vinylammonium bis(pentafluoroethanesulfonyl)imide, N,N,N-trialkyl-N-vinylammonium tris(trifluoromethanesulfonyl)imide, N,N,N-trialkyl-N-vinylammonium hexafluorophosphate, N,N,N-trialkyl-N-vinylammonium (trifluoromethanesulfonyl)trifluoroacetamide, N,N,N-trialkyl-N-vinylammonium dicyanamide, and N,N,N-trialkyl-N-vinylammonium thiocyanate;N,N,N-Trialkyl-N-(meth)acryloyloxyalkylammonium tetrafluoroborate, N,N,N-Trialkyl-N-(meth)acryloyloxyalkylammonium trifluoroacetate, N,N,N-Trialkyl-N-(meth)acryloyloxyalkylammonium heptafluorobutyrate, N,N,N-Trialkyl-N-(meth)acryloyloxyalkylammonium trifluoromethanesulfonate, N,N,N-Trialkyl-N-(meth)acryloyloxyalkylammonium perfluorobutanesulfonate, N,N,N-Trialkyl-N-(meth)acryloyloxyalkylammonium bis(trifluoromethanesulfonyl)imide, N,N,N-Trialkyl-N-(meth)acryloyloxyalkylammonium ammonium bis(pentafluoroethanesulfonyl)imide, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium tris(trifluoromethanesulfonyl)imide, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium hexafluorophosphate, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium (trifluoromethanesulfonyl)trifluoroacetamide, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium dicyanamide, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium thiocyanate, and other N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium cation-containing ionic compounds;N,N,N-Trialkyl-N-(meth)acryloylaminoalkylammonium tetrafluoroborate, N,N,N-Trialkyl-N-(meth)acryloylaminoalkylammonium trifluoroacetate, N,N,N-Trialkyl-N-(meth)acryloylaminoalkylammonium heptafluorobutyrate, N,N,N-Trialkyl-N-(meth)acryloylaminoalkylammonium trifluoromethanesulfonate, N,N,N-Trialkyl-N-(meth)acryloylaminoalkylammonium perfluorobutanesulfonate, N,N,N-Trialkyl-N-(meth)acryloylaminoalkylammonium bis(trifluoromethanesulfonyl)imide, N,N,N-Trialkyl-N-(meth)acryloylaminoalkylammonium Examples of N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium cation-containing ionic compounds include bis(pentafluoroethanesulfonyl)imide, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium tris(trifluoromethanesulfonyl)imide, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium hexafluorophosphate, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium(trifluoromethanesulfonyl)trifluoroacetamide, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium dicyanamide, and N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.

[0097] Among the ionic monomers represented by the general formula (A), X + is a quaternary ammonium group, and n 1 is 1 and n 2 is 0 and A 1is a (meth)acryloyloxy group, preferred examples include (meth)acryloyloxypropyltrimethylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxypropyldimethylbenzylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxyethyltrimethylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxyethyldimethylbenzylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxyethyltrimethylammonium bis(fluorosulfonyl)imide, (meth)acryloyloxyethyldimethylbenzylammonium bis(fluorosulfonyl)imide, (meth)acryloyloxyethyltrimethylammonium trifluoromethanesulfonic acid, and (meth)acryloyloxyethyldimethylbenzylammonium trifluoromethanesulfonic acid.

[0098] Among the ionic monomers represented by the general formula (A), X + is a quaternary ammonium group, and n 1 is 1 and n 2 is 0 and A 1 is a (meth)acryloylamino group, preferred examples include (meth)acryloylaminopropyltrimethylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloylaminopropyldimethylbenzylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloylaminopropyltrimethylammonium bis(fluorosulfonyl)imide, (meth)acryloylaminopropyldimethylbenzylammonium bis(fluorosulfonyl)imide, (meth)acryloylaminopropyltrimethylammonium trifluoromethanesulfonate, and (meth)acryloylaminopropyldimethylbenzylammonium trifluoromethanesulfonate.

[0099] Among the ionic monomers represented by the general formula (A), X + is an imidazolium group, and n 1is 1 and n 2 is 0 or 1, and A 1 and A 2Specific examples of the embodiment in which is a vinyl group include 1-alkyl-3-vinylimidazolium tetrafluoroborate, 1-alkyl-3-vinylimidazolium trifluoroacetate, 1-alkyl-3-vinylimidazolium heptafluorobutyrate, 1-alkyl-3-vinylimidazolium trifluoromethanesulfonate, 1-alkyl-3-vinylimidazolium perfluorobutanesulfonate, 1-alkyl-3-vinylimidazolium bis(trifluoromethanesulfonyl)imide, 1-alkyl-3-vinylimidazolium Ionic compounds containing 1-alkyl-3-vinylimidazolium cations such as bis(pentafluoroethanesulfonyl)imide, 1-alkyl-3-vinylimidazolium tris(trifluoromethanesulfonyl)imide, 1-alkyl-3-vinylimidazolium hexafluorophosphate, 1-alkyl-3-vinylimidazolium (trifluoromethanesulfonyl)trifluoroacetamide, 1-alkyl-3-vinylimidazolium dicyanamide, and 1-alkyl-3-vinylimidazolium thiocyanate; 1,2-dialkyl- Ionic compounds containing 1,2-dialkyl-3-vinylimidazolium cations, such as 3-vinylimidazolium bis(fluorosulfonyl)imide, 1,2-dialkyl-3-vinylimidazolium bis(trifluoromethanesulfonyl)imide, 1,2-dialkyl-3-vinylimidazolium dicyanamide, and 1,2-dialkyl-3-vinylimidazolium thiocyanate; 2-alkyl-1,3-divinylimidazolium bis(fluorosulfonyl)imide, 2-alkyl-1,3-divinylimidazolium bis(trifluoromethanesulfonyl)imide, ionic compounds containing a 2-alkyl-1,3-divinylimidazolium cation such as 1-vinylimidazolium bis(fluorosulfonyl)imide, 1-vinylimidazolium bis(trifluoromethanesulfonyl)imide, 1-vinylimidazolium dicyanamide, and 2-alkyl-1,3-divinylimidazolium thiocyanate; and ionic compounds containing a 1-vinylimidazolium cation such as 1-vinylimidazolium bis(fluorosulfonyl)imide, 1-vinylimidazolium bis(trifluoromethanesulfonyl)imide, 1-vinylimidazolium dicyanamide, and 1-vinylimidazolium thiocyanate.

[0100] Among the ionic monomers represented by the general formula (A), X + is an imidazolium group, and n 1 is 1 and n 2 is 0 or 1, and A 1 and A 2Specific examples of the embodiment in which is a (meth)acryloyloxy group include 1-alkyl-3-(meth)acryloyloxyalkylimidazolium tetrafluoroborate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium trifluoroacetate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium heptafluorobutyrate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium trifluoromethanesulfonate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium tetrafluoroborate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium trifluoroacetate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium heptafluorobutyrate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium trifluoromethanesulfonate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium tetrafluoroborate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium trifluoromethanesulfonate ... Acryloyloxyalkylimidazolium perfluorobutanesulfonate, 1-Alkyl-3-(meth)acryloyloxyalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1-Alkyl-3-(meth)acryloyloxyalkylimidazolium bis(pentafluoroethanesulfonyl)imide, 1-Alkyl-3-(meth)acryloyloxyalkylimidazolium tris(trifluoromethanesulfonyl)imide, 1-Alkyl-3-(meth)acryloyloxyalkylimidazolium tris(trifluoromethanesulfonyl)imide 1-Alkyl-3-(meth)acryloyloxyalkylimidazolium cation-containing ionic compounds such as 1-alkyl-3-(meth)acryloyloxyalkylimidazolium hexafluorophosphate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium (trifluoromethanesulfonyl)trifluoroacetamide, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium dicyanamide, and 1-alkyl-3-(meth)acryloyloxyalkylimidazolium thiocyanate; 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium cation-containing ionic compounds such as 1-alkyl-3-(meth)acryloyloxyalkylimidazolium hexafluorophosphate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium (trifluoromethanesulfonyl)trifluoroacetamide, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium dicyanamide, and 1-alkyl-3-(meth)acryloyloxyalkylimidazolium thiocyanate; ionic compounds containing 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium cations, such as 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium bis(fluorosulfonyl)imide, 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium dicyanamide, and 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium thiocyanate;2-Alkyl-1,3-di(meth)acryloyloxyalkylimidazolium bis(fluorosulfonyl)imide, 2-alkyl-1,3-di(meth)acryloyloxyalkylimidazolium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1,3-di(meth)acryloyloxyalkylimidazolium dicyanamide, 2-alkyl-1,3-di(meth)acryloyloxyimidazolium thiocyanate, etc. Ionic compounds containing midazolium cations include ionic compounds containing 1-(meth)acryloyloxyalkylimidazolium cations such as 1-(meth)acryloyloxyalkylimidazolium bis(fluorosulfonyl)imide, 1-(meth)acryloyloxyalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1-(meth)acryloyloxyalkylimidazolium dicyanamide, and 1-(meth)acryloyloxyalkylimidazolium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.

[0101] Among the ionic monomers represented by the general formula (A), X + is an imidazolium group, and n 1 is 1 and n 2 is 0 or 1, and A 1 and A 2Specific examples of the embodiment in which is a (meth)acryloylamino group include 1-alkyl-3-(meth)acryloylaminoalkylimidazolium tetrafluoroborate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluoroacetate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium heptafluorobutyrate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluoromethanesulfonate, ...methanesulfonate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium tetrafluoroborate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluoromethanesulfonate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium tetrafluoroborate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluoromethanesulfonate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluoromethanesulfonate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluoromethanesulfonate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluoromethanesulfonate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluorom Acryloylaminoalkylimidazolium perfluorobutanesulfonate, 1-Alkyl-3-(meth)acryloylaminoalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1-Alkyl-3-(meth)acryloylaminoalkylimidazolium bis(pentafluoroethanesulfonyl)imide, 1-Alkyl-3-(meth)acryloylaminoalkylimidazolium tris(trifluoromethanesulfonyl)imide, 1-Alkyl-3-(meth)acryloylaminoalkylimidazolium tris(trifluoromethanesulfonyl)imide 1-Alkyl-3-(meth)acryloylaminoalkylimidazolium cation-containing ionic compounds such as 1-alkyl-3-(meth)acryloylaminoalkylimidazolium hexafluorophosphate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium (trifluoromethanesulfonyl)trifluoroacetamide, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium dicyanamide, and 1-alkyl-3-(meth)acryloylaminoalkylimidazolium thiocyanate; 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium cation-containing ionic compounds such as 1-alkyl-3-(meth)acryloylaminoalkylimidazolium hexafluorophosphate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium (trifluoromethanesulfonyl)trifluoroacetamide, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium dicyanamide, and 1-alkyl-3-(meth)acryloylaminoalkylimidazolium thiocyanate; ionic compounds containing 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium cations, such as 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium bis(fluorosulfonyl)imide, 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium dicyanamide, and 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium thiocyanate;2-Alkyl-1,3-di(meth)acryloylaminoalkylimidazolium bis(fluorosulfonyl)imide, 2-alkyl-1,3-di(meth)acryloylaminoalkylimidazolium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1,3-di(meth)acryloylaminoalkylimidazolium dicyanamide, 2-alkyl-1,3-di(meth)acryloylaminoimidazolium thiocyanate, etc. Ionic compounds containing midazolium cations include ionic compounds containing 1-(meth)acryloylaminoalkylimidazolium cations such as 1-(meth)acryloylaminoalkylimidazolium bis(fluorosulfonyl)imide, 1-(meth)acryloylaminoalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1-(meth)acryloylaminoalkylimidazolium dicyanamide, and 1-(meth)acryloylaminoalkylimidazolium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.

[0102] Among the ionic monomers represented by the general formula (A), X + is a pyridinium group, and n 1 is 1 and n 2 is 0 and A 1Specific examples of the embodiment in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include 1-vinylpyridinium cation-containing ionic compounds such as 1-vinylpyridinium bis(fluorosulfonyl)imide, 1-vinylpyridinium bis(trifluoromethanesulfonyl)imide, 1-vinylpyridinium dicyanamide, and 1-vinylpyridinium thiocyanate; 1-(meth)acryloyloxyalkylpyridinium bis(fluorosulfonyl)imide, 1-(meth)acryloyloxyalkylpyridinium bis(trifluoromethanesulfonyl)imide, and the like. 1-(meth)acryloyloxyalkylpyridinium cation-containing ionic compounds such as 1-(meth)acryloyloxyalkylpyridinium bis(trifluoromethanesulfonyl)imide, 1-(meth)acryloyloxyalkylpyridinium dicyanamide, and 1-(meth)acryloyloxyalkylpyridinium thiocyanate; 1-(meth)acryloylaminoalkylpyridinium bis(fluorosulfonyl)imide, 1-(meth)acryloylaminoalkylpyridinium bis(trifluoromethane ... and 1-(meth)acryloylaminoalkylpyridinium thiocyanate; Ionic compounds containing 1-(meth)acryloylaminoalkylpyridinium cations, such as 2-alkyl-1-vinylpyridinium bis(fluorosulfonyl)imide, 2-alkyl-1-vinylpyridinium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1-vinylpyridinium dicyanamide, and 2-alkyl-1-vinylpyridinium thiocyanate; 2-alkyl-1-vinylpyridinium cations, such as 2-alkyl-1-vinylpyridinium bis(fluorosulfonyl)imide, 2-alkyl-1-vinylpyridinium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1-vinylpyridinium dicyanamide, and 2-alkyl-1-vinylpyridinium thiocyanate. Ionic compounds containing 2-alkyl-1-(meth)acryloyloxyalkylpyridinium cations, such as 2-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(fluorosulfonyl)imide, 2-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1-(meth)acryloyloxyalkylpyridinium dicyanamide, and 2-alkyl-1-(meth)acryloyloxyalkylpyridinium thiocyanate;Ionic compounds containing 2-alkyl-1-(meth)acryloylaminoalkylpyridinium cations, such as 2-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(fluorosulfonyl)imide, 2-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1-(meth)acryloylaminoalkylpyridinium dicyanamide, and 2-alkyl-1-(meth)acryloylaminoalkylpyridinium thiocyanate; ionic compounds containing 3-alkyl-1-vinylpyridinium cations, such as 3-alkyl-1-vinylpyridinium bis(fluorosulfonyl)imide, 3-alkyl-1-vinylpyridinium bis(trifluoromethanesulfonyl)imide, 3-alkyl-1-vinylpyridinium dicyanamide, and 3-alkyl-1-vinylpyridinium thiocyanate; and ionic compounds containing 3-alkyl-1-vinylpyridinium cations, such as 3-alkyl-1-(meth)acryloyloxyalkylpyridinium bis 3-Alkyl-1-(meth)acryloyloxyalkylpyridinium cation-containing ionic compounds such as (fluorosulfonyl)imide, 3-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(trifluoromethanesulfonyl)imide, 3-alkyl-1-(meth)acryloyloxyalkylpyridinium dicyanamide, and 3-alkyl-1-(meth)acryloyloxyalkylpyridinium thiocyanate; 3-Alkyl-1-(meth)acryloylaminoalkylpyridinium bis(fluorosulfonyl)imide, 3-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(trifluoromethanesulfonyl)imide, 3-alkyl-1-(meth)acryloylaminoalkylpyridinium dicyanamide, and 3-alkyl-1-(meth)acryloylaminoalkylpyridinium thiocyanate; 3-Alkyl-1-(meth)acryloylaminoalkylpyridinium cation-containing ionic compounds such as 3-Alkyl-1-(meth)acryloylaminoalkylpyridinium bis(trifluoromethanesulfonyl)imide, 3-Alkyl-1-(meth)acryloylaminoalkylpyridinium dicyanamide, and 3-Alkyl-1-(meth)acryloylaminoalkylpyridinium thiocyanate;4-Alkyl-1-vinylpyridinium cation-containing ionic compounds such as 4-alkyl-1-vinylpyridinium bis(fluorosulfonyl)imide, 4-alkyl-1-vinylpyridinium bis(trifluoromethanesulfonyl)imide, 4-alkyl-1-vinylpyridinium dicyanamide, and 4-alkyl-1-vinylpyridinium thiocyanate; 4-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(fluorosulfonyl)imide, 4-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(trifluoromethanesulfonyl)imide, 4-alkyl-1-(meth)acryloyloxyalkylpyridinium dicyanamide, and 4-alkyl-1-(meth)acryloyloxyalkylpyridinium thiocyanate; p) 4-alkyl-1-(meth)acryloyloxyalkylpyridinium cation-containing ionic compounds such as acryloyloxyalkylpyridinium thiocyanate; 4-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(fluorosulfonyl)imide, 4-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(trifluoromethanesulfonyl)imide, 4-alkyl-1-(meth)acryloylaminoalkylpyridinium dicyanamide, 4-alkyl-1-(meth)acryloylaminoalkylpyridinium thiocyanate, and other 4-alkyl-1-(meth)acryloylaminoalkylpyridinium cation-containing ionic compounds. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.

[0103] Among the ionic monomers represented by the general formula (A), X + is a piperidinium group, and n 1 is 1 and n 2 is 0 and A 1Specific examples of the embodiment in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include 1-alkyl-1-vinylalkylpiperidinium cation-containing ionic compounds such as 1-alkyl-1-vinylalkylpiperidinium bis(fluorosulfonyl)imide, 1-alkyl-1-vinylalkylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-alkyl-1-vinylalkylpiperidinium dicyanamide, and 1-alkyl-1-vinylalkylpiperidinium thiocyanate; 1-alkyl-1-(meth)acryloyloxyalkylpiperidinium bis(fluorosulfonyl)imide, 1-alkyl-1-(meth)acryloyloxyalkylpiperidinium bis(trifluoromethane ... Examples of the ionic compounds include 1-alkyl-1-(meth)acryloyloxyalkylpiperidinium cation-containing ionic compounds such as 1-acryloyloxyalkylpiperidinium dicyanamide and 1-alkyl-1-(meth)acryloyloxyalkylpiperidinium thiocyanate; and 1-alkyl-1-(meth)acryloylaminoalkylpiperidinium cation-containing ionic compounds such as 1-alkyl-1-(meth)acryloylaminoalkylpiperidinium bis(fluorosulfonyl)imide, 1-alkyl-1-(meth)acryloylaminoalkylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-alkyl-1-(meth)acryloylaminoalkylpiperidinium dicyanamide and 1-alkyl-1-(meth)acryloylaminoalkylpiperidinium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.

[0104] Among the ionic monomers represented by the general formula (A), X + is a pyrrolidinium group, and n 1 is 1 and n 2 is 0 and A 1Specific examples of the embodiment in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include 1-alkyl-1-vinylalkylpyrrolidinium cation-containing ionic compounds such as 1-alkyl-1-vinylalkylpyrrolidinium bis(fluorosulfonyl)imide, 1-alkyl-1-vinylalkylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-alkyl-1-vinylalkylpyrrolidinium dicyanamide, and 1-alkyl-1-vinylalkylpyrrolidinium thiocyanate; 1-alkyl-1-(meth)acryloyloxyalkylpyrrolidinium bis(fluorosulfonyl)imide, 1-alkyl-1-(meth)acryloyloxyalkylpyrrolidinium bis(trifluoromethane ...thiocyanate, and the like. Examples of the ionic compounds include 1-alkyl-1-(meth)acryloyloxyalkylpyrrolidinium cation-containing ionic compounds such as 1-acryloyloxyalkylpyrrolidinium dicyanamide and 1-alkyl-1-(meth)acryloyloxyalkylpyrrolidinium thiocyanate; and 1-alkyl-1-(meth)acryloylaminoalkylpyrrolidinium cation-containing ionic compounds such as 1-alkyl-1-(meth)acryloylaminoalkylpyrrolidinium bis(fluorosulfonyl)imide, 1-alkyl-1-(meth)acryloylaminoalkylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-alkyl-1-(meth)acryloylaminoalkylpyrrolidinium dicyanamide and 1-alkyl-1-(meth)acryloylaminoalkylpyrrolidinium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.

[0105] Among the ionic monomers represented by the general formula (A), X + is a trialkylsulfonium group, and n 1 is 1 and n 2 is 0 and A 1Specific examples of the embodiment in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include dialkyl(vinyl)sulfonium cation-containing ionic compounds such as dialkyl(vinyl)sulfonium bis(fluorosulfonyl)imide, dialkyl(vinyl)sulfonium bis(trifluoromethanesulfonyl)imide, dialkyl(vinyl)sulfonium dicyanamide, and dialkyl(vinyl)sulfonium thiocyanate; dialkyl((meth)acryloyloxyalkyl)sulfonium bis(fluorosulfonyl)imide, dialkyl((meth)acryloyloxyalkyl)sulfonium bis(trifluoromethanesulfonyl)imide, dialkyl((meth)acryloyloxyalkyl)sulfonium bis(trifluoromethanesulfonyl)imide, dialkyl((meth)acryloyloxyalkyl) Examples of suitable alkyl substituents include dialkyl((meth)acryloyloxyalkyl)sulfonium cation-containing ionic compounds such as dialkyl((meth)acryloyloxyalkyl)sulfonium dicyanamide and dialkyl((meth)acryloyloxyalkyl)sulfonium thiocyanate; and dialkyl((meth)acryloylaminoalkyl)sulfonium cation-containing ionic compounds such as dialkyl((meth)acryloylaminoalkyl)sulfonium bis(fluorosulfonyl)imide, dialkyl((meth)acryloylaminoalkyl)sulfonium bis(trifluoromethanesulfonyl)imide, dialkyl((meth)acryloylaminoalkyl)sulfonium dicyanamide and dialkyl((meth)acryloylaminoalkyl)sulfonium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.

[0106] Among the ionic monomers represented by the general formula (A), X + is a quaternary phosphonium group, and n 1 is 1 and n 2 is 0 and A 1Specific examples of the embodiment in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include trialkyl(vinyl)phosphonium cation-containing ionic compounds such as trialkyl(vinyl)phosphonium bis(fluorosulfonyl)imide, trialkyl(vinyl)phosphonium bis(trifluoromethanesulfonyl)imide, trialkyl(vinyl)phosphonium dicyanamide, and trialkyl(vinyl)phosphonium thiocyanate; trialkyl((meth)acryloyloxyalkyl)phosphonium bis(fluorosulfonyl)imide, trialkyl((meth)acryloyloxyalkyl)phosphonium bis(trifluoromethanesulfonyl)imide, trialkyl((meth)acryloyloxyalkyl)phosphonium bis(trifluoromethanesulfonyl)imide, trialkyl((meth)acryloyloxyalkyl) )phosphonium dicyanamide, trialkyl((meth)acryloyloxyalkyl)phosphonium thiocyanate, and other ionic compounds containing a trialkyl((meth)acryloyloxyalkyl)phosphonium cation; trialkyl((meth)acryloylaminoalkyl)phosphonium bis(fluorosulfonyl)imide, trialkyl((meth)acryloylaminoalkyl)phosphonium bis(trifluoromethanesulfonyl)imide, trialkyl((meth)acryloylaminoalkyl)phosphonium dicyanamide, trialkyl((meth)acryloylaminoalkyl)phosphonium thiocyanate, and other ionic compounds containing a trialkyl((meth)acryloylaminoalkyl)phosphonium cation. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.

[0107] The content (ratio) of the ionic monomer in all monomer units of the conductive segment (B) (total amount of monomer components constituting the conductive segment (B)) is not particularly limited, but from the viewpoint of being able to impart excellent antistatic properties to the pressure-sensitive adhesive layer of the present invention, it is preferably 1 to 20 parts by weight, more preferably 3 to 15 parts by weight, and even more preferably 5 to 10 parts by weight relative to the total amount (100 parts by weight) of monomer components constituting the conductive segment (B).

[0108] The content (proportion) of the ionic monomer in all monomer units of the block copolymer of the present invention (total amount of monomer components constituting the block copolymer) is not particularly limited, but in order to impart sufficient antistatic performance to the pressure-sensitive adhesive layer of the present invention, it may be contained in an amount of preferably 0.01 part by weight or more, more preferably 0.05 part by weight or more, even more preferably 0.1 part by weight or more, 0.5 part by weight or more, 1.0 part by weight or more, 2.0 parts by weight or more, 3.0 parts by weight or more, 4.0 parts by weight or more, or 5.0 parts by weight or more, relative to 100 parts by weight (total amount) of the block copolymer of the present invention. Furthermore, the content (proportion) of the ionic monomer is not particularly limited, but in order to facilitate ensuring transparency, appearance, durability such as adhesion reliability in the pressure-sensitive adhesive layer of the present invention, it may be contained in an amount of preferably 50 parts by weight or less, more preferably 40 parts by weight or less, even more preferably 30 parts by weight or less, 25 parts by weight or less, 20 parts by weight or less, or 15 parts by weight or less, relative to 100 parts by weight of the block copolymer of the present invention.

[0109] [1-9. Method for preparing the block copolymer of the present invention] The block copolymer of the present invention can be produced by living radical polymerization of the above-mentioned monomer components. Living radical polymerization is preferred in that it maintains the simplicity and versatility of conventional radical polymerization methods, while being less susceptible to termination reactions and chain transfer, and allows growth without deactivation of growing ends, making it easy to precisely control the molecular weight distribution and produce polymers with uniform composition.

[0110] In the living radical polymerization method, the adhesive segment (A) may be produced first, and then a monomer for the conductive segment (B) may be polymerized onto the adhesive segment (A); or the conductive segment (B) may be produced first, and then a monomer for the adhesive segment (A) may be polymerized onto the conductive segment (B).

[0111] When the block copolymer of the present invention is an ABA triblock copolymer, it is preferable, from the viewpoint of ease of production, to produce the A segment first and then polymerize the B segment monomer onto the A segment.

[0112] The living radical polymerization method can be any known method without particular limitation, and depending on the method for stabilizing the polymer growing end, there are methods such as a method using a transition metal catalyst (ATRP method), a method using a sulfur-based reversible addition-fragmentation chain transfer agent (RAFT agent) (RAFT method), and a method using an organotellurium compound (TERP method). Among these methods, the RAFT method is preferred from the viewpoints of the variety of monomers that can be used, ease of molecular weight control, and the absence of metal residues in the pressure-sensitive adhesive composition.

[0113] The RAFT method can be any known method without any particular limitation, and may include, for example, step 1 (first RAFT polymerization) of preparing a first segment by polymerizing a monomer component using a RAFT agent, and step 2 (second RAFT polymerization) of adding a second segment to the first segment obtained in step 1 by further adding and polymerizing a monomer component having a different monomer composition from that in step 1. After the second RAFT polymerization, third, fourth, etc. RAFT polymerizations may be further performed in the same manner as the second RAFT polymerization to add third, fourth, etc. segments.

[0114] Steps 1 and 2 can be carried out by known and commonly used methods, such as solution polymerization, emulsion polymerization, bulk polymerization, and polymerization methods using heat or active energy ray irradiation (thermal polymerization, active energy ray polymerization). Among these, solution polymerization is preferred in terms of transparency, water resistance, cost, etc. Note that the polymerization is preferably carried out while avoiding contact with oxygen in order to suppress polymerization inhibition by oxygen. For example, the polymerization is preferably carried out under a nitrogen atmosphere.

[0115] When the block copolymer of the present invention is an ABA triblock copolymer, it is preferable to prepare the copolymer by preparing an A segment in the step 1 and then adding a B segment to the obtained A segment in the step 2. In this case, it is preferable that the A segment is an adhesive segment (A) and the B segment is a conductive segment (B).

[0116] The RAFT agent can be any known agent without any particular limitation, and is preferably, for example, a compound represented by the following formula (a), formula (b), or formula (c) (trithiocarbonate, dithioester, dithiocarbonate). [ka] [ka] [ka]

[0117] In formula (a), formula (b), or formula (c) [formulas (a) to (c)], R 1a and R 1b are the same or different and represent a hydrogen atom, a hydrocarbon group, or a cyano group. 1c represents a hydrocarbon group which may have a cyano group. 1a , R 1b , and R 1c Examples of hydrocarbon groups as R include hydrocarbon groups having 1 to 20 carbon atoms (such as linear, branched, or cyclic saturated or unsaturated hydrocarbon groups), and among these, hydrocarbon groups having 1 to 12 carbon atoms are preferred. Specific examples of the hydrocarbon groups include linear, branched, or cyclic alkyl groups having 1 to 18 carbon atoms (preferably 1 to 12 carbon atoms), such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, and octadecyl; aryl groups having 6 to 12 carbon atoms, such as phenyl; and arylalkyl groups having a total of 7 to 10 carbon atoms, such as benzyl and phenethyl. 1c Examples of the hydrocarbon group having a cyano group as the aryl group include groups in which 1 to 3 hydrogen atoms of the hydrocarbon group mentioned above have been substituted with cyano groups.

[0118] In formulas (a) to (c), R 2represents a hydrocarbon group or a group in which some of the hydrogen atoms of the hydrocarbon group have been substituted with carboxyl groups (for example, a carboxyalkyl group). Examples of the hydrocarbon group include hydrocarbon groups having 1 to 20 carbon atoms (such as linear, branched, or cyclic saturated or unsaturated hydrocarbon groups), and among these, hydrocarbon groups having 1 to 12 carbon atoms are preferred. Specific examples of the hydrocarbon group include linear, branched, or cyclic alkyl groups having 1 to 18 carbon atoms (preferably 1 to 12 carbon atoms), such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, and octadecyl; and arylalkyl groups having a total of 7 to 10 carbon atoms, such as benzyl and phenethyl.

[0119] In the RAFT method, polymerization proceeds by a reaction in which the raw material monomer is inserted between the sulfur atom in the RAFT agent represented by formulas (a) to (c) and the methylene group adjacent to the sulfur atom.

[0120] Many of the RAFT agents are commercially available. Those that are not commercially available can be easily synthesized by known or conventional methods. In the present invention, the RAFT agents can be used alone or in combination of two or more.

[0121] Examples of RAFT agents include trithiocarbonates such as dibenzyl trithiocarbonate and S-cyanomethyl-S-dodecyl trithiocarbonate; dithioesters such as cyanoethyl dithiopropionate, benzyl dithiopropionate, benzyl dithiobenzoate, and acetoxyethyl dithiobenzoate; and dithiocarbonates such as O-ethyl-S-(1-phenylethyl)dithiocarbonate, O-ethyl-S-(2-propoxyethyl)dithiocarbonate, and O-ethyl-S-(1-cyano-1-methylethyl)dithiocarbonate. Of these, trithiocarbonates are preferred, and trithiocarbonates having a bilaterally symmetrical structure in formula (a) are more preferred. Dibenzyl trithiocarbonate and bis{4-[ethyl-(2-acetyloxyethyl)carbamoyl]benzyl}trithiocarbonate are particularly preferred.

[0122] Step 1 can be carried out by polymerizing the monomer components in the presence of a RAFT agent. The amount of the RAFT agent used in Step 1 is usually 0.05 to 20 parts by weight, and preferably 0.05 to 10 parts by weight, per 100 parts by weight of the total amount of the monomer components. Such an amount makes it easy to control the reaction and also to control the weight-average molecular weight of the resulting segment. The step 2 can be carried out by adding a monomer component to the polymerization reaction mixture obtained in the step 1 and further polymerizing the mixture.

[0123] The RAFT method is preferably carried out in the presence of a polymerization initiator. Examples of the polymerization initiator include ordinary organic polymerization initiators, specifically peroxides and azo compounds, and among these, azo compounds are preferred. The polymerization initiator can be used alone or in combination of two or more.

[0124] Examples of peroxide polymerization initiators include benzoyl peroxide and tert-butyl permaleate. Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4- Dimethylvaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis(isobutylamide) dihydrate, 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis(2-cyanopropanol), dimethyl-2,2'-azobis(2-methylpropionate), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide].

[0125] The amount of the polymerization initiator used is usually 0.001 to 2 parts by weight, and preferably 0.002 to 1 part by weight, relative to 100 parts by weight of the total amount of the monomer components. With such an amount, it is easy to control the weight-average molecular weight of the resulting segment.

[0126] The RAFT method may be bulk polymerization without using a polymerization solvent, but preferably uses a polymerization solvent. Examples of the polymerization solvent include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenylethyl ether, and diphenyl ether; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and sulfolane. The polymerization solvents can be used alone or in combination of two or more.

[0127] The amount of the polymerization solvent used is not particularly limited, and is, for example, preferably 0.01 mL or more, more preferably 0.05 mL or more, and even more preferably 0.1 mL or more, per 1 g of the monomer component, and is preferably 50 mL or less, more preferably 10 mL or less, and even more preferably 1 mL or less.

[0128] The reaction temperature in the RAFT method is usually 60 to 120°C, preferably 70 to 110°C, and is usually carried out under an inert gas atmosphere such as nitrogen gas. This reaction can be carried out under any condition of normal pressure, increased pressure, or reduced pressure, and is usually carried out under normal pressure. The reaction time is usually 1 to 20 hours, preferably 2 to 14 hours.

[0129] The polymerization reaction conditions for the RAFT method described above can be applied to Step 1 and Step 2, respectively.

[0130] After the polymerization reaction is completed, the target block copolymer of the present invention can be separated from the resulting reaction mixture by removing the solvent used and residual monomers by conventional separation and purification means.

[0131] When the adhesive segment (A) or the conductive segment (B) of the block copolymer of the present invention is prepared in the above step 1, the weight average molecular weight (Mw) of the adhesive segment (A) or the conductive segment (B) is not particularly limited, but is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and even more preferably 100,000 to 300,000. Having the Mw of the adhesive segment (A) or the conductive segment (B) within this range is suitable for achieving the above-mentioned effects of the present invention. When two or more adhesive segments (A) or conductive segments (B) are present in the block copolymer of the present invention, the above Mw is the sum of the Mw of the adhesive segments (A) or conductive segments (B).

[0132] The weight average molecular weight (Mw) of the block copolymer of the present invention is not particularly limited, but is preferably 200,000 or more, more preferably 300,000 to 5,000,000, and even more preferably 400,000 to 2,500,000. Having the Mw of the block copolymer of the present invention within this range is suitable for achieving the effects of the present invention described above.

[0133] The molecular weight distribution (Mw / Mn) of the block copolymer of the present invention is not particularly limited, but is preferably greater than 1, more preferably 1.5 or more, even more preferably 2 or more, particularly preferably 2.5 or more, and is preferably 5 or less, more preferably 4.5 or less, even more preferably 4 or less, particularly preferably 3.5 or less.

[0134] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) are measured by the GPC method.

[0135] The content of the adhesive segment (A) in all monomer units of the block copolymer of the present invention (total amount of monomer components constituting the block copolymer) is not particularly limited, but is preferably 1 to 50 wt %, more preferably 3 to 45 wt %, and even more preferably 5 to 40 wt %. A configuration in which the content of the adhesive segment (A) is 1 wt % or more is preferable in that it can impart excellent adhesiveness to the pressure-sensitive adhesive layer of the present invention. Furthermore, a configuration in which the content of the adhesive segment (A) is 50 wt % or less is preferable in that it can form a sea-island structure in which the pressure-sensitive adhesive composition of the present invention is phase-separated into a continuous phase and a discontinuous phase.

[0136] The content of the conductive segment (B) in all monomer units of the block copolymer of the present invention (total amount of monomer components constituting the block copolymer) is not particularly limited, but is preferably 50 to 99 wt %, more preferably 55 to 97 wt %, and even more preferably 60 to 95 wt %. A configuration in which the content of the conductive segment (B) is 50 wt % or more is preferable in that the pressure-sensitive adhesive composition of the present invention can form a sea-island structure in which the pressure-sensitive adhesive composition is phase-separated into a continuous phase and a discontinuous phase. Furthermore, a configuration in which the content of the conductive segment (B) is 99 wt % or less is preferable in that excellent adhesiveness can be imparted to the pressure-sensitive adhesive layer of the present invention.

[0137] In the block copolymer of the present invention, the weight ratio of the conductive segment (B) to the adhesive segment (A) (conductive segment (B) / adhesive segment (A)) is preferably 50 / 50 to 99 / 1. A weight ratio of 50 / 50 or more is preferred in that the pressure-sensitive adhesive composition of the present invention can form a sea-island structure in which the adhesive composition is phase-separated into a continuous phase and a discontinuous phase, and is more preferably 55 / 45 or more, even more preferably 60 / 40 or more, and particularly preferably 65 / 35 or more. A weight ratio of 99 / 1 or less is preferred in that excellent adhesiveness can be imparted to the pressure-sensitive adhesive layer of the present invention, and is more preferably 97 / 3 or less, even more preferably 95 / 5 or less, and particularly preferably 93 / 7 or less.

[0138] The content and ratio of each segment can be calculated from the amount of monomer components used in each step of the RAFT method, and can be controlled by the monomer charging ratio when forming each segment and the polymerization rate of each monomer, etc.

[0139] [1-10. Antistatic agents] The pressure-sensitive adhesive composition of the present invention may contain an antistatic agent within a range that does not impair the effects of the present invention. Examples of the antistatic agent include materials capable of imparting antistatic properties, such as ionic compounds, ionic surfactants, conductive polymers, conductive fine particles, etc. Among these, ionic compounds are preferred in terms of compatibility with the block copolymer of the present invention and transparency of the pressure-sensitive adhesive layer.

[0140] As the ionic compound, inorganic cation anion salts and / or organic cation anion salts can be preferably used, and the use of inorganic cation anion salts is particularly preferred. Ionic compounds containing inorganic cations (inorganic cation anion salts) are more preferable than organic cation anion salts because, when used, they can suppress a decrease in the adhesion (anchoring strength) of the pressure-sensitive adhesive layer. In the present invention, the term "inorganic cation anion salt" generally refers to an alkali metal salt formed from an alkali metal cation and an anion. The alkali metal salt can be an organic salt or an inorganic salt of an alkali metal. In the present invention, the term "organic cation anion salt" refers to an organic salt whose cation moiety is composed of an organic substance, and whose anion moiety may be either organic or inorganic. "Organic cation anion salts" are also referred to as ionic liquids or ionic solids. As the anion component constituting the ionic compound, those using a fluorine-containing anion are preferred in terms of antistatic function.

[0141] Examples of alkali metal ions that constitute the cation moiety of the alkali metal salt include lithium ions, sodium ions, and potassium ions, with lithium ions being preferred among these alkali metal ions.

[0142] The anion portion of the alkali metal salt may be composed of an organic substance or an inorganic substance. Examples of the anion portion constituting the organic salt include CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (CF3SO2)3C - , C4F9SO3 - , C3F7COO - , (CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - , PF6 - , CO3 2- , or the following general formulas (1) to (4): (1):(C n F 2n+1 SO2)2N - (where n is an integer from 1 to 10), (2):CF2(C m F 2m SO2)2N - (where m is an integer from 1 to 10), (3): - O3S(CF2) l SO3 - (where l is an integer from 1 to 10), (4):(C p F 2p+1 SO2)N - (C q F 2q+1 SO2), (where p and q are integers from 1 to 10), and (FSO2)2N - In particular, an anion moiety containing a fluorine atom is preferably used because it can produce an ionic compound with good ionic dissociation properties. Examples of an anion moiety constituting an inorganic salt include Cl - , Br - , I - , AlCl4 - , Al2Cl7 - , BF4 - , PF6 - , ClO4 - , NO3 - , AsF6 - , SbF6 -, NbF6 - , TaF6 - , (CN)2N - , etc. are used. Among anions containing fluorine atoms, fluorine-containing imide anions are preferred, and among these, bis(trifluoromethanesulfonyl)imide anions and bis(fluorosulfonyl)imide anions are preferred. In particular, bis(fluorosulfonyl)imide anions are preferred because they can impart excellent antistatic properties with the addition of a relatively small amount, maintain adhesive properties, and are advantageous in durability under humid and heated environments.

[0143] Specific examples of organic salts of alkali metals include sodium acetate, sodium alginate, sodium lignosulfonate, sodium toluenesulfonate, LiCF3SO3, Li(CF3SO2)2N, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, KO3S(CF2)3SO3K, and LiO3S(CF2)3SO3K. Of these, LiCF 3SO3, Li(FSO2)2N, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, etc. are preferred, and fluorine-containing lithium imide salts such as Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N are more preferred, with lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide being particularly preferred.

[0144] Examples of inorganic salts of alkali metals include lithium perchlorate and lithium iodide.

[0145] The organic cation-anion salt is composed of a cation component and an anion component, and the cation component is an organic substance. Specific examples of the cation component include pyridinium cation, piperidinium cation, pyrrolidinium cation, cation having a pyrroline skeleton, cation having a pyrrole skeleton, imidazolium cation, tetrahydropyrimidinium cation, dihydropyrimidinium cation, pyrazolium cation, pyrazolinium cation, tetraalkylammonium cation, trialkylsulfonium cation, and tetraalkylphosphonium cation.

[0146] Examples of anion components include Cl - , Br - , I - , AlCl4 - , Al2Cl7 - , BF4 - , PF6 - , ClO4 - , NO3 - , CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (CF3SO 2 )3C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , (CN)2N - , C4F9SO3 - , C3F7COO - , ((CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - , or the following general formulas (1) to (4): (1):(C n F 2n+1 SO2)2N - (where n is an integer from 1 to 10), (2):CF2(C m F 2m SO2)2N - (where m is an integer from 1 to 10), (3):- O3S(CF2) l SO3 - (where l is an integer from 1 to 10), (4):(C p F 2p+1 SO2)N - (C q F 2q+1 SO2), (where p and q are integers from 1 to 10), and (FSO2)2N - Examples of anions that can be used include those represented by the formula:

[0023] . Among these, anions containing fluorine atoms (fluorine-containing anions) are particularly preferred because they can yield ionic compounds with good ionic dissociation properties. Among anions containing fluorine atoms, fluorine-containing imide anions are preferred, and among these, bis(trifluoromethanesulfonyl)imide anions and bis(fluorosulfonyl)imide anions are preferred. In particular, bis(fluorosulfonyl)imide anions are preferred because they can impart excellent antistatic properties with the addition of a relatively small amount, maintain adhesive properties, and are advantageous in durability under humid and heated environments.

[0147] In addition to the inorganic cation anion salts (alkali metal salts) and organic cation anion salts, examples of the ionic compounds include inorganic salts such as ammonium chloride, aluminum chloride, copper chloride, ferrous chloride, ferric chloride, ammonium sulfate, etc. These ionic compounds can be used alone or in combination.

[0148] Ionic surfactants include various types of surfactants, such as cationic surfactants (e.g., quaternary ammonium salts, phosphonium salts, sulfonium salts, etc.), anionic surfactants (carboxylic acid, sulfonate, sulfate, phosphate, phosphite, etc.), amphoteric surfactants (sulfobetaine, alkylbetaine, alkylimidazolium betaine, etc.), and nonionic surfactants (polyhydric alcohol derivatives, β-cyclodextrin inclusion compounds, sorbitan fatty acid monoesters and diesters, polyalkylene oxide derivatives, amine oxides, etc.).

[0149] Examples of conductive polymers include polyaniline-based, polythiophene-based, polypyrrole-based, and polyquinoxaline-based polymers, and among these, polyaniline and polythiophene are preferably used, with polythiophene being particularly preferred.

[0150] Examples of conductive fine particles include metal oxides such as tin oxide, antimony oxide, indium oxide, and zinc oxide. Of these, tin oxide is preferred. Examples of tin oxide include tin oxide, antimony-doped tin oxide, indium-doped tin oxide, aluminum-doped tin oxide, tungsten-doped tin oxide, a titanium oxide-cerium oxide-tin oxide composite, and a titanium oxide-tin oxide composite. The average particle size of the fine particles is about 1 to 100 nm, preferably 2 to 50 nm.

[0151] Further examples of antistatic agents other than those mentioned above include acetylene black, ketjen black, natural graphite, artificial graphite, titanium black, homopolymers of monomers having cationic (quaternary ammonium salts, etc.), amphoteric (betaine compounds, etc.), anionic (sulfonate salts, etc.) or nonionic (glycerin, etc.) ion-conductive groups or copolymers of such monomers with other monomers, ionic conductive polymers such as polymers having moieties derived from acrylates or methacrylates having quaternary ammonium salt groups, and permanent antistatic agents of the type in which hydrophilic polymers such as polyethylene methacrylate copolymers are alloyed with acrylic resins or the like.

[0152] When the pressure-sensitive adhesive composition of the present invention contains the antistatic agent, the content thereof is not particularly limited, but from the viewpoint of ensuring the transparency, appearance, durability such as adhesion reliability of the pressure-sensitive adhesive layer of the present invention, it is preferably 1 part by weight or less, more preferably 0.5 parts by weight or less, 0.4 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less, per 100 parts by weight of the total amount of the block copolymer of the present invention. When the pressure-sensitive adhesive composition of the present invention contains the antistatic agent, the lower limit of the content thereof is not particularly limited, but it may be 0.01 parts by weight or more, or 0.05 parts by weight or more, per 100 parts by weight of the total amount of the block copolymer of the present invention.

[0153] [1-11. Additives] The pressure-sensitive adhesive composition of the present invention may contain, as necessary, known additives such as crosslinking agents, crosslinking accelerators, silane coupling agents, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antioxidants, fillers, colorants (pigments, dyes, etc.), UV absorbers, antioxidants, chain transfer agents, plasticizers, softeners, surfactants, and rust inhibitors, within limits that do not impair the properties of the present invention. These additives may be used alone or in combination of two or more.

[0154] When the pressure-sensitive adhesive composition of the present invention contains a crosslinking agent, the block copolymer of the present invention is crosslinked to increase the gel fraction, which facilitates improving the foam-peeling resistance. Furthermore, the sea-island structure described below is more easily formed. For example, by crosslinking the block copolymer of the present invention, the gel fraction can be easily controlled and increased, which facilitates improving the foam-peeling resistance.

[0155] Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, and amine-based crosslinking agents. Among these, when the pressure-sensitive adhesive composition of the present invention forms a pressure-sensitive adhesive layer containing an acrylic polymer as the base polymer, isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred, and isocyanate-based crosslinking agents are more preferred, from the viewpoint of improving foaming and peeling resistance. The crosslinking agents may be used alone or in combination of two or more.

[0156] Examples of the isocyanate-based crosslinking agent (polyfunctional isocyanate compound) include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate. Examples of the isocyanate crosslinking agent include commercially available products such as a trimethylolpropane / tolylene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate L"), a trimethylolpropane / hexamethylene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate HL"), and a trimethylolpropane / xylylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., trade name "Takenate D-110N").

[0157] Examples of the epoxy crosslinking agent (polyfunctional epoxy compound) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycol Examples of the epoxy crosslinking agent include adipic acid diglycidyl ester, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Examples of the epoxy crosslinking agent include commercially available products such as "Tetrad C" manufactured by Mitsubishi Gas Chemical Company, Inc.

[0158] The content of the crosslinking agent in the pressure-sensitive adhesive composition of the present invention is not particularly limited, but is preferably 0.001 to 10 parts by weight, more preferably 0.01 to 5 parts by weight, per 100 parts by weight of the block copolymer of the present invention. A crosslinking agent content of 0.001 part by weight or more is preferred because it tends to improve foaming and peeling resistance. On the other hand, a crosslinking agent content of 10 parts by weight or less is preferred because it tends to provide the pressure-sensitive adhesive layer with appropriate flexibility and improve adhesive strength.

[0159] The pressure-sensitive adhesive composition of the present invention preferably contains a silane coupling agent, since this facilitates obtaining excellent adhesion to glass (particularly excellent adhesion reliability to glass under high temperature and high humidity conditions). Examples of the silane coupling agent include, but are not limited to, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-phenyl-aminopropyltrimethoxysilane. Of these, γ-glycidoxypropyltrimethoxysilane is preferred. Further examples of the silane coupling agent include commercially available products such as "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.). The silane coupling agents may be used alone or in combination of two or more.

[0160] The content of the silane coupling agent in the pressure-sensitive adhesive composition of the present invention is not particularly limited. For example, when the pressure-sensitive adhesive composition of the present invention is a pressure-sensitive adhesive layer containing an acrylic polymer as a base polymer, the content is preferably 0.01 to 1 part by weight, more preferably 0.03 to 0.5 parts by weight, per 100 parts by weight of the block copolymer of the present invention, from the viewpoint of improving adhesive reliability to glass.

[0161] It is preferable that the pressure-sensitive adhesive composition of the present invention contains a colorant (pigment, dye, etc.), as this can prevent reflection from metal wiring or metal oxides such as ITO, and can also contribute to preventing RGB color mixing and improving contrast.

[0162] The colorant may be a dye or a pigment as long as it is soluble or dispersible in the pressure-sensitive adhesive composition of the present invention. Dyes are preferred because they can achieve low haze even with a small amount of addition, do not settle like pigments, and are easily distributed uniformly. Pigments are also preferred because they provide high color expression even with a small amount of addition. When using a pigment as a colorant, it is preferable that it has low or no conductivity. When using a dye, it is preferable to use it in combination with an antioxidant, etc.

[0163] Examples of pigments include "9050BLACK" and "UVBK-0001" manufactured by Tokushiki, carbon black, titanium black, etc. Examples of dyes include "VALIFAST BLACK 3810" and "NUBIAN Black PA-2802" manufactured by Orient Chemical Industries, Ltd.

[0164] The content of the colorant in the pressure-sensitive adhesive composition of the present invention is, for example, about 0.01 to 20 parts by weight relative to 100 parts by weight of the block copolymer of the present invention, and may be appropriately set depending on the type of colorant, the color tone and light transmittance of the pressure-sensitive adhesive layer, etc. The colorant may be added to the composition as a solution or dispersion obtained by dissolving or dispersing the colorant in an appropriate solvent.

[0165] [1-12.Sea-island structure] The pressure-sensitive adhesive composition of the present invention has a sea-island structure in which the pressure-sensitive adhesive composition is phase-separated into a continuous phase and a discontinuous phase. The configuration in which the pressure-sensitive adhesive composition of the present invention has a sea-island structure is preferred in that paths for imparting conductivity are efficiently formed in the continuous phase, and the pressure-sensitive adhesive layer of the present invention exhibits low surface resistivity and excellent antistatic performance.

[0166] The "island-sea structure" refers to a structure in which a discontinuous phase (islands) made of at least one polymer out of two or more polymers is dispersed in a continuous phase (sea) made of another polymer. The island-sea structure can be confirmed by observing thin sections prepared from a frozen sample using a transmission electron microscope (TEM).

[0167] The sea-island structure is thought to be formed when, in the block copolymer contained in the pressure-sensitive adhesive composition of the present invention, adhesive segments (A) gather together through pseudo-crosslinking, and conductive segments (B) gather together through pseudo-crosslinking, forming phases that separate.Which of the phase derived from the adhesive segment (A) or the phase derived from the conductive segment (B) forms the continuous phase (sea portion) or the discontinuous phase (island portion) is not particularly limited, and can be adjusted by adjusting the type of block copolymer, the monomer composition and amount, the type of each segment, adhesive segment (A) and conductive segment (B), the monomer composition and amount, the type and amount of crosslinking agent, etc.

[0168] In the pressure-sensitive adhesive composition of the present invention, the continuous phase (sea portion) preferably contains the conductive segment (B). A configuration in which the continuous phase (sea portion) contains the conductive segment (B) is preferred in that paths for imparting conductivity are efficiently formed in the continuous phase (sea portion), and the pressure-sensitive adhesive layer of the present invention exhibits low surface resistivity and excellent antistatic performance.

[0169] In the pressure-sensitive adhesive composition of the present invention, the discontinuous phase (island portion) preferably contains the adhesive segment (A). A configuration in which the discontinuous phase (island portion) contains the adhesive segment (A) is preferable in that excellent adhesiveness can be imparted to the pressure-sensitive adhesive layer of the present invention without impairing excellent antistatic performance.

[0170] The configuration in which the continuous phase (sea portion) contains the conductive segment (B) and the configuration in which the discontinuous phase (island portion) contains the adhesive segment (A) can be realized by adjusting the type of block copolymer in the pressure-sensitive adhesive composition of the present invention, the monomer composition and amount, the type of each segment of the adhesive segment (A) and the conductive segment (B), the monomer composition and amount, the type and amount of the crosslinking agent, etc.

[0171] [2. Adhesive layer] The pressure-sensitive adhesive layer of the present invention is a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention. The pressure-sensitive adhesive layer of the present invention has excellent antistatic properties. Therefore, when an image display device and an optical member are bonded together via the pressure-sensitive adhesive layer of the present invention, display defects caused by static electricity can be suppressed. Thus, the pressure-sensitive adhesive layer of the present invention is suitably used in the manufacture of image display devices.

[0172] The surface resistivity (according to JIS K 6271) of the pressure-sensitive adhesive layer of the present invention (a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention) is preferably 1.0 × 10 11 Ω / □ or less, and more preferably 0.5×10 11 Ω / □ or less, and more preferably 1.0×10 10 Ω / □ or less, 0.5×10 10 The lower limit of the surface resistivity of the pressure-sensitive adhesive layer of the present invention is not particularly limited, but is preferably 1.0×10 5 Ω / □ or more, or 0.5×10 5 It may be Ω / □ or more.

[0173] The surface resistivity of the pressure-sensitive adhesive layer of the present invention can be measured by the method described in the Examples below. The surface resistivity of the pressure-sensitive adhesive layer of the present invention can be adjusted by adjusting the type of block copolymer, the monomer composition and amount, the type of each segment of the pressure-sensitive adhesive segment (A) and the conductive segment (B), the monomer composition and amount, the type and amount of the crosslinking agent, etc.

[0174] The pressure-sensitive adhesive layer of the present invention (a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention) is transparent or has transparency. Therefore, the pressure-sensitive adhesive layer of the present invention has excellent visibility and appearance through the pressure-sensitive adhesive layer. Thus, the pressure-sensitive adhesive layer of the present invention is suitably used for optical purposes.

[0175] The haze (according to JIS K7136) of the pressure-sensitive adhesive layer of the present invention (a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention) is not particularly limited, but is preferably 3% or less, more preferably 1% or less, 0.7% or less, or 0.6% or less. A haze of 3% or less is preferable because excellent transparency and excellent appearance can be obtained. The haze can be measured, for example, by forming a pressure-sensitive adhesive layer (thickness: 100 μm), leaving it at room temperature (23° C., 50% RH) for at least 24 hours, and then bonding it to a slide glass (e.g., having a total light transmittance of 92% and a haze of 0.2%) to form a sample, using a haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., trade name "HM-150N").

[0176] The total light transmittance (according to JIS K7361-1) in the visible light wavelength region of the pressure-sensitive adhesive layer of the present invention is not particularly limited, but is preferably 90% or more, more preferably 91% or more, or may be 92% or more. A total light transmittance of 90% or more is preferable, as excellent transparency and excellent appearance can be obtained. The total light transmittance can be measured, for example, by forming a pressure-sensitive adhesive layer (thickness: 100 μm), leaving it at room temperature (23° C., 50% RH) for at least 24 hours, peeling off a release liner if present, and bonding the layer to a slide glass (e.g., one with a total light transmittance of 92% and a haze of 0.2%) as a sample, using a haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., product name "HM-150N").

[0177] The total light transmittance and haze of the pressure-sensitive adhesive layer of the present invention can be measured by the methods described in the Examples below. The total light transmittance and haze of the pressure-sensitive adhesive layer of the present invention can be adjusted by the type of block copolymer, the monomer composition and amount, the type of each segment of the pressure-sensitive adhesive segment (A) and the conductive segment (B), the monomer composition and amount, the type and amount of the crosslinking agent, etc.

[0178] The gel fraction (proportion of solvent-insoluble components) of the pressure-sensitive adhesive layer of the present invention is not particularly limited, but is preferably 40 to 95%, more preferably 50 to 92%, and even more preferably 55 to 90%. A gel fraction of 40% or more improves the cohesive strength of the pressure-sensitive adhesive layer, suppressing foaming and peeling at the interface with the adherend in high-temperature environments, dents during handling, and contamination of edges during processing, making it easier to achieve excellent foaming and peeling resistance, which is preferable. A gel fraction of 95% or less is also preferable, as it provides appropriate flexibility and further improves adhesion and conformability to uneven surfaces.

[0179] Specifically, the gel fraction (proportion of solvent-insoluble components) is a value calculated by the following "Method for measuring gel fraction," for example.

[0180] Approximately 0.1 g of the adhesive layer was sampled from the adhesive sheet, wrapped in a porous tetrafluoroethylene sheet (trade name "NTF1122", manufactured by Nitto Denko Corporation) with an average pore size of 0.2 μm, and then tied with kite string. The weight at this time was measured, and this weight was defined as the weight before immersion. The weight before immersion was the total weight of the adhesive layer (the adhesive layer sampled above), the tetrafluoroethylene sheet, and the kite string. The total weight of the tetrafluoroethylene sheet and the kite string was also measured, and this weight was defined as the wrapping weight. Next, the pressure-sensitive adhesive layer is wrapped in a tetrafluoroethylene sheet and tied with kite string (referred to as the "sample"), which is placed in a 50 ml container filled with ethyl acetate and allowed to stand for 7 days at 23° C. Thereafter, the sample (after ethyl acetate treatment) is removed from the container, transferred to an aluminum cup, and dried in a dryer at 130° C. for 2 hours to remove the ethyl acetate, after which the sample is weighed and this weight is defined as the post-immersion weight. Then, the gel fraction is calculated using the following formula. Gel fraction [% (weight%)] = (XY) / (ZY) × 100

[0181] The gel fraction can be adjusted, for example, by the type of block copolymer, the monomer composition and amount, the type of each segment of the adhesive segment (A) and the conductive segment (B), the monomer composition and amount, the type and amount of the crosslinking agent, etc.

[0182] The storage modulus of the pressure-sensitive adhesive layer of the present invention at 25°C and 1 Hz is not particularly limited, but is preferably 3×10 4 The pressure-sensitive adhesive layer of the present invention preferably has a storage modulus of 3×10 Pa or more at 25° C. and 1 Hz. 4 A storage modulus of the pressure-sensitive adhesive layer of the present invention at 25° C. and 1 Hz of 5×10 or more is preferred in that it is less likely to cause dents during handling. 4 Pa or more is more preferable, 1×10 5 The upper limit of the storage modulus at 25°C and 1 Hz of the pressure-sensitive adhesive layer of the present invention is not particularly limited. However, from the viewpoint of the step-following ability of the pressure-sensitive adhesive layer of the present invention, it is preferably 5 × 10 6 Pa or less is preferable, and 1×10 6 It may be less than Pa.

[0183] The storage modulus of the pressure-sensitive adhesive sheet of the present invention at 25°C and 1 Hz can be measured by dynamic viscoelasticity measurement. The storage modulus of the pressure-sensitive adhesive sheet of the present invention at 25°C and 1 Hz can be adjusted by the type of block copolymer, the monomer composition and amount, the type of each segment of the pressure-sensitive adhesive segment (A) and the conductive segment (B), the monomer composition and amount, the type and amount of the crosslinking agent, etc.

[0184] The thickness of the pressure-sensitive adhesive layer of the present invention is not particularly limited, but is preferably 5 to 250 μm, and more preferably 7 to 240 μm, 10 to 230 μm, 12 to 220 μm, 15 to 210 μm, 20 to 200 μm, 23 to 175 μm, or 25 to 150 μm. A thickness of at least a certain level is preferred because it improves step-following ability and adhesive reliability. A thickness of no more than a certain level is preferred because it is particularly excellent in handleability and manufacturability.

[0185] The method for producing the pressure-sensitive adhesive layer of the present invention is not particularly limited. For example, the pressure-sensitive adhesive layer can be produced by preparing the pressure-sensitive adhesive composition (precursor composition) of the present invention, and then, if necessary, irradiating it with active energy rays, drying it by heating, etc. Specifically, the pressure-sensitive adhesive layer can be produced by adding the above-mentioned crosslinking agent, additives, etc. to the block copolymer of the present invention, if necessary, and mixing them.

[0186] The method for producing the pressure-sensitive adhesive layer of the present invention is not particularly limited, but examples include coating (applying) the pressure-sensitive adhesive composition onto a substrate or a release liner, and then drying, curing, or drying and curing, as necessary.

[0187] The pressure-sensitive adhesive composition may be applied (coated) using a known coating method, such as a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, spray coater, comma coater, or direct coater.

[0188] [3. Adhesive sheet] The pressure-sensitive adhesive sheet of the present invention has a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention. The pressure-sensitive adhesive sheet of the present invention is not particularly limited in other respects as long as it has the pressure-sensitive adhesive layer of the present invention (a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention).

[0189] The pressure-sensitive adhesive sheet of the present invention may be a double-sided pressure-sensitive adhesive sheet in which both sides are pressure-sensitive adhesive layer surfaces, or a single-sided pressure-sensitive adhesive sheet in which only one side is a pressure-sensitive adhesive layer surface. Among these, a double-sided pressure-sensitive adhesive sheet is preferred from the viewpoint of bonding two members together. Note that, in this specification, the term "pressure-sensitive adhesive sheet" also includes tape-like materials, i.e., "pressure-sensitive adhesive tape." Also, in this specification, the pressure-sensitive adhesive layer surface may be referred to as the "adhesive surface."

[0190] The pressure-sensitive adhesive sheet of the present invention may have a release liner provided on the adhesive surface until use.

[0191] The pressure-sensitive adhesive sheet of the present invention may be a so-called "substrate-less" pressure-sensitive adhesive sheet that does not have a substrate (substrate layer) (hereinafter, this may be referred to as a "substrate-less pressure-sensitive adhesive sheet"), or may be a pressure-sensitive adhesive sheet that has a substrate (hereinafter, this may be referred to as a "substrate-attached pressure-sensitive adhesive sheet"). Examples of the substrate-less pressure-sensitive adhesive sheet include a double-sided pressure-sensitive adhesive sheet consisting of only the pressure-sensitive adhesive layer, and a double-sided pressure-sensitive adhesive sheet consisting of the pressure-sensitive adhesive layer and a pressure-sensitive adhesive layer other than the pressure-sensitive adhesive layer (hereinafter, this may be referred to as an "other pressure-sensitive adhesive layer"). On the other hand, examples of substrate-attached pressure-sensitive adhesive sheets include pressure-sensitive adhesive sheets having the pressure-sensitive adhesive layer on at least one side of a substrate. Of these, substrate-less pressure-sensitive adhesive sheets (substrate-less double-sided pressure-sensitive adhesive sheets) are preferred, and substrate-less double-sided pressure-sensitive adhesive sheets consisting of only the pressure-sensitive adhesive layer are more preferred. Note that the "substrate (substrate layer)" does not include a release liner that is peeled off during use (application) of the pressure-sensitive adhesive sheet. The pressure-sensitive adhesive sheet of the present invention is preferably a substrate-less pressure-sensitive adhesive sheet.

[0192] One embodiment of the pressure-sensitive adhesive sheet of the present invention (substrate-less pressure-sensitive adhesive sheet) is shown in Fig. 1. In the pressure-sensitive adhesive sheet of Fig. 1, 10 denotes a pressure-sensitive adhesive layer, and 11 and 12 denote release liners.

[0193] [3-1. Various physical properties of adhesive sheets] The 180° peel adhesion strength of the pressure-sensitive adhesive sheet of the present invention to a glass plate at 23°C (particularly the 180° peel adhesion strength of the adhesive surface provided by the pressure-sensitive adhesive layer (the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention) to a glass plate at 23°C) is not particularly limited, but from the viewpoint that a high adhesive strength provides sufficient adhesion, it is preferably 4 N / 20 mm or more, more preferably 6 N / 20 mm or more, even more preferably 8 N / 20 mm or more, and even more preferably 10 N / 20 mm or more. When the 180° peel adhesion strength of the pressure-sensitive adhesive sheet of the present invention to a glass plate at 23°C is a certain value or more, the adhesiveness to glass and the ability to prevent lifting at steps are even better. The upper limit of the 180° peel adhesive strength of the pressure-sensitive adhesive sheet of the present invention against a glass plate at 23°C is not particularly limited, but is preferably, for example, 28 N / 20 mm, 27 N / 20 mm, or 26 N / 20 mm, and more preferably 25 N / 20 mm, 24 N / 20 mm, 23 N / 20 mm, 22 N / 20 mm, 21 N / 20 mm, or 20 N / 20 mm.

[0194] The 180° peel adhesive strength of the pressure-sensitive adhesive sheet of the present invention to a glass plate at 80°C (particularly the 180° peel adhesive strength of the adhesive surface provided by the pressure-sensitive adhesive layer (the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention) to a glass plate at 80°C) is not particularly limited, but from the viewpoint that a high adhesive strength provides sufficient adhesion, it is preferably 4 N / 20 mm or more, more preferably 6 N / 20 mm or more, even more preferably 8 N / 20 mm or more, and even more preferably 10 N / 20 mm or more. If the pressure-sensitive adhesive sheet of the present invention has a 180° peel adhesive strength to a glass plate at 80°C of a certain value or more, the adhesiveness to glass and the ability to prevent lifting at steps will be even more excellent. The upper limit of the 180° peel adhesive strength of the pressure-sensitive adhesive sheet of the present invention to a glass plate at 80°C is not particularly limited, but is, for example, preferably 18 N / 20 mm, more preferably 16 N / 20 mm. The 180° peel adhesive strength to a glass plate at 23°C or 80°C is determined by the following 180° peel adhesive strength measurement method.

[0195] The glass plate is not particularly limited, but examples thereof include the product name "Soda Lime Glass #0050" (manufactured by Matsunami Glass Industry Co., Ltd.) Other examples include alkali-free glass and chemically strengthened glass.

[0196] (A-1. 180° peel adhesive strength measurement method) The adhesive side of the pressure-sensitive adhesive sheet is attached to the adherend, pressed back and forth with a 2 kg roller, and aged for 30 minutes or 240 hours in an atmosphere of 23°C and 50% RH. After aging, the pressure-sensitive adhesive sheet is peeled from the adherend in accordance with JIS Z 0237 under conditions of 23°C or 80°C, 50% RH, a pulling speed of 300 mm / min, and a peel angle of 180°, and the 180° peel adhesive strength (N / 20 mm) is measured.

[0197] (B. Thickness) The thickness (total thickness) of the pressure-sensitive adhesive sheet of the present invention is not particularly limited, but is preferably 12 to 350 μm, and more preferably 15 to 330 μm, 18 to 325 μm, 18 to 320 μm, 20 to 300 μm, 23 to 300 μm, 25 to 275 μm, or 30 to 250 μm. A thickness of at least a certain level is preferred because peeling at uneven areas is less likely to occur. Furthermore, a thickness of no more than a certain level is preferred because excellent appearance is more easily maintained during production. The thickness of the pressure-sensitive adhesive sheet of the present invention includes the thickness of the substrate in the case of a substrate-attached pressure-sensitive adhesive sheet, but does not include the thickness of the release liner.

[0198] (C. Hayes) The haze (according to JIS K7136) of the pressure-sensitive adhesive sheet of the present invention is not particularly limited, but is preferably 3% or less, and more preferably 1% or less, 0.7% or less, or 0.6% or less. A haze of 3% or less is preferable because excellent transparency and excellent appearance can be obtained. The haze can be measured, for example, by leaving the pressure-sensitive adhesive sheet at room temperature (23°C, 50% RH) for at least 24 hours, peeling off a release liner if present, and bonding the sheet to a slide glass (e.g., one with a total light transmittance of 92% and a haze of 0.2%) as a sample, using a haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., product name "HM-150N").

[0199] (D.Total light transmittance) The total light transmittance (according to JIS K7361-1) in the visible light wavelength region of the pressure-sensitive adhesive sheet of the present invention is not particularly limited, but is preferably 90% or more, more preferably 91% or more, or even 92% or more. A total light transmittance of 90% or more is preferable, as excellent transparency and excellent appearance can be obtained. The total light transmittance can be measured, for example, by leaving the pressure-sensitive adhesive sheet at room temperature (23°C, 50% RH) for at least 24 hours, peeling off a release liner if present, and bonding the sheet to a slide glass (e.g., one with a total light transmittance of 92% and a haze of 0.2%) as a sample using a haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., product name "HM-150N").

[0200] The adhesive strength, total light transmittance, and haze of the pressure-sensitive adhesive sheet of the present invention can be measured by the methods described in the Examples below. The adhesive strength, total light transmittance, and haze of the pressure-sensitive adhesive sheet of the present invention can be adjusted by the type of block copolymer, the monomer composition and amount, the type of each segment of the adhesive segment (A) and the conductive segment (B), the monomer composition and amount, and the type and amount of the crosslinking agent.

[0201] [3-2. Manufacturing method of adhesive sheet] The pressure-sensitive adhesive sheet of the present invention is not particularly limited, but is preferably produced according to a known or conventional production method. For example, when the pressure-sensitive adhesive sheet of the present invention is a substrate-less pressure-sensitive adhesive sheet, it can be obtained by forming the pressure-sensitive adhesive layer on a release liner by the above-mentioned method. Furthermore, when the pressure-sensitive adhesive sheet of the present invention is a substrate-attached pressure-sensitive adhesive sheet, it can be obtained by forming the pressure-sensitive adhesive layer directly on the surface of the substrate (direct transfer method), or by forming the pressure-sensitive adhesive layer on a release liner and then transferring (laminating) it to the substrate to provide the pressure-sensitive adhesive layer on the substrate (transfer method).

[0202] [3-3. Other layers of the adhesive sheet] The pressure-sensitive adhesive sheet of the present invention may have other layers in addition to the pressure-sensitive adhesive layer. Examples of other layers include other pressure-sensitive adhesive layers (pressure-sensitive adhesive layers other than the pressure-sensitive adhesive layer (pressure-sensitive adhesive layers other than the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention)), intermediate layers, undercoat layers, etc. The pressure-sensitive adhesive sheet of the present invention may have two or more other layers.

[0203] [3-4. Adhesive sheet substrate] When the pressure-sensitive adhesive sheet of the present invention is a substrate-attached pressure-sensitive adhesive sheet, the substrate is not particularly limited, and examples thereof include various optical films such as plastic films, antireflection (AR) films, polarizing plates, and retardation plates. Examples of materials for the plastic films include polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymers, and cyclic olefin polymers such as "ARTON (cyclic olefin polymer, manufactured by JSR Corporation)" and "ZEONOR (cyclic olefin polymer, manufactured by Zeon Corporation)." These plastic materials may be used alone or in combination of two or more. Furthermore, the "substrate" refers to the portion that is attached to the adherend together with the adhesive layer when the pressure-sensitive adhesive sheet is attached to the adherend. The "substrate" does not include a release liner that is peeled off during use (application) of the pressure-sensitive adhesive sheet.

[0204] The substrate is preferably transparent. The total light transmittance (according to JIS K7361-1) of the substrate in the visible light wavelength region is not particularly limited, but is preferably 85% or more, more preferably 88% or more. The haze (according to JIS K7136) of the substrate is not particularly limited, but is preferably 1.0% or less, more preferably 0.8% or less. Examples of such transparent substrates include PET films and non-oriented films such as those sold under the trade names "Arton" and "Zeonor."

[0205] The thickness of the substrate is not particularly limited, but is preferably 1 to 500 μm. The substrate may have either a single layer or multiple layers. The surface of the substrate may be appropriately subjected to a known and commonly used surface treatment, such as a physical treatment such as corona discharge treatment or plasma treatment, or a chemical treatment such as a primer treatment.

[0206] [3-5. Release liner for adhesive sheets] The pressure-sensitive adhesive sheet of the present invention may have a release liner on its adhesive surface until use. When the pressure-sensitive adhesive sheet of the present invention is a double-sided pressure-sensitive adhesive sheet, each adhesive surface may be protected by two release liners, or may be protected by a single release liner with release surfaces on both sides and wound into a roll. The release liner is used as a protective material for the pressure-sensitive adhesive layer and is peeled off when the sheet is attached to the adherend. When the pressure-sensitive adhesive sheet of the present invention is a substrate-less pressure-sensitive adhesive sheet, the release liner also serves as a support for the pressure-sensitive adhesive layer. The release liner is not necessarily provided.

[0207] As the release liner, conventional release paper or the like can be used. Specifically, for example, in addition to a substrate having a release treatment layer formed on at least one surface using a release treatment agent, a low-adhesion substrate made of a fluorine-based polymer (e.g., polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc.) or a low-adhesion substrate made of a non-polar polymer (e.g., an olefin-based resin such as polyethylene or polypropylene, etc.) can be used.

[0208] As the release liner, for example, a release liner having a release treatment layer formed on at least one surface of a release liner substrate can be suitably used. Examples of such release liner substrates include plastic substrate films (synthetic resin films) such as polyester films (polyethylene terephthalate films, etc.), olefin resin films (polyethylene films, polypropylene films, etc.), polyvinyl chloride films, polyimide films, polyamide films (nylon films), and rayon films, as well as papers (high-quality paper, Japanese paper, kraft paper, glassine paper, synthetic paper, top-coated paper, etc.), and multilayered products (2- to 3-layer composites) obtained by laminating or coextruding these.

[0209] The release treatment agent constituting the release treatment layer is not particularly limited, but examples thereof include silicone-based release treatment agents, fluorine-based release treatment agents, long-chain alkyl-based release treatment agents, etc. Release treatment agents can be used alone or in combination of two or more.

[0210] The thickness of the release liner is not particularly limited and may be appropriately selected from the range of 5 to 100 μm.

[0211] The release liner may have an antistatic layer formed on at least one surface of the release liner substrate to prevent damage to the adherend, such as an image display panel, etc. The antistatic layer may be formed on one surface of the release liner (the release-treated surface or the untreated surface), or on both surfaces of the release liner (the release-treated surface and the untreated surface).

[0212] The antistatic layer is not particularly limited, but may be, for example, an antistatic layer formed by coating a release liner with a conductive coating liquid containing a conductive polymer. Specifically, it may be, for example, an antistatic layer formed by coating a release liner (release-treated surface and / or untreated surface) with a conductive coating liquid containing a conductive polymer. Specific coating methods include roll coating, bar coating, and gravure coating.

[0213] As the conductive polymer, a polyaniline-based, polythiophene-based, polypyrrole-based, polyquinoxaline-based polymer or the like can be used.

[0214] The thickness of the antistatic layer is preferably 1 nm to 1000 nm, more preferably 5 nm to 900 nm. The antistatic layer may be a single layer or may be two or more layers.

[0215] [3-6. Uses of adhesive sheets] The pressure-sensitive adhesive sheet of the present invention has the pressure-sensitive adhesive layer (a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention), and therefore has excellent antistatic properties. Therefore, when used to attach an image display device, display defects due to static electricity are unlikely to occur. Therefore, the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention can satisfy excellent antistatic properties, transparency, moist heat resistance, and low contamination, and is useful for manufacturing image display devices.

[0216] Furthermore, the pressure-sensitive adhesive layer of the present invention has excellent adhesion, anti-foaming peeling properties, and stress relaxation properties, as well as excellent step-following properties and adhesive reliability, particularly at high temperatures. It also has excellent appearance. Therefore, the pressure-sensitive adhesive sheet of the present invention is useful for adherends that are prone to foaming at the interface at high temperatures. For example, polymethyl methacrylate resin (PMMA) may contain unreacted monomers, which can easily cause foaming due to foreign matter at high temperatures. Furthermore, polycarbonate (PC) is prone to outgassing of water and carbon dioxide at high temperatures. Because the pressure-sensitive adhesive sheet of the present invention has excellent anti-foaming peeling properties, it is also useful for plastic adherends that contain such resins.

[0217] Furthermore, the pressure-sensitive adhesive sheet of the present invention is useful not only for adherends with a small linear expansion coefficient but also for adherends with a large linear expansion coefficient. The adherend with a small linear expansion coefficient is not particularly limited, but for example, a glass plate (linear expansion coefficient: 0.3×10 -5 ~0.8×10 -5 / ℃), polyethylene terephthalate substrate (PET film, linear expansion coefficient: 1.5×10 -5 ~2×10 -5 The adherend having a large linear expansion coefficient is not particularly limited, but examples thereof include resin substrates having a large linear expansion coefficient, and more specifically, polycarbonate resin substrates (PC, linear expansion coefficient: 7×10 -5 ~8×10 -5 / ℃), polymethyl methacrylate resin substrate (PMMA, linear expansion coefficient: 7×10 -5 ~8×10 -5 / ℃), cycloolefin polymer substrate (COP, coefficient of linear expansion: 6×10 -5 ~7×10-5 / °C), trade name "ZEONOR" (manufactured by Zeon Corporation), trade name "ARTON" (manufactured by JSR Corporation), and the like.

[0218] The pressure-sensitive adhesive sheet of the present invention is useful for bonding an adherend having a small linear expansion coefficient to an adherend having a large linear expansion coefficient. Specifically, the pressure-sensitive adhesive sheet of the present invention is preferably used for bonding a glass adherend (e.g., glass plate, chemically strengthened glass, glass lens, etc.) to the above-mentioned resin substrate having a large linear expansion coefficient.

[0219] Thus, the pressure-sensitive adhesive sheet of the present invention is useful for bonding adherends made of various materials together, and is particularly useful for bonding a glass adherend to a plastic adherend. The plastic adherend may be an optical film such as a plastic film having an ITO (indium tin oxide) layer on its surface.

[0220] Furthermore, the pressure-sensitive adhesive sheet of the present invention is useful not only for adherends with smooth surfaces but also for adherends with uneven surfaces. In particular, the pressure-sensitive adhesive sheet of the present invention is useful for bonding a glass adherend to the resin substrate with a high linear expansion coefficient, even if at least one of the glass adherend and the resin substrate with a high linear expansion coefficient has uneven surfaces.

[0221] The pressure-sensitive adhesive sheet of the present invention is preferably used in the manufacture of portable electronic devices, such as mobile phones, PHSs, smartphones, tablets (tablet computers), mobile computers (mobile PCs), personal digital assistants (PDAs), electronic organizers, portable broadcast receivers such as portable televisions and portable radios, portable game consoles, portable audio players, portable DVD players, cameras such as digital cameras, and camcorder-type video cameras.

[0222] The pressure-sensitive adhesive sheet of the present invention is preferably used, for example, for bonding components or modules constituting a portable electronic device together, or for fixing components or modules constituting a portable electronic device to a housing. More specifically, examples of such applications include bonding a cover glass or lens (especially a glass lens) to a touch panel or touch sensor, fixing a cover glass or lens (especially a glass lens) to a housing, fixing a display panel to a housing, fixing an input device such as a sheet-like keyboard or a touch panel to a housing, bonding a protective panel of an information display unit to a housing, bonding housings together, bonding a housing to a decorative sheet, and fixing or bonding various components or modules constituting a portable electronic device. In this specification, the term "display panel" refers to a structure composed of at least a lens (especially a glass lens) and a touch panel. Furthermore, the term "lens" as used herein is a concept that encompasses both transparent bodies that exhibit light refraction and transparent bodies that do not. In other words, the term "lens" as used herein also encompasses a simple window panel that does not exhibit refraction.

[0223] Furthermore, the pressure-sensitive adhesive sheet of the present invention is preferably used for optical applications. That is, the pressure-sensitive adhesive sheet of the present invention is preferably an optical pressure-sensitive adhesive sheet used for optical applications. More specifically, it is preferably used for, for example, bonding optical components (for bonding optical components) or for manufacturing products (optical products) using the optical components.

[0224] [4. Optical Components] The pressure-sensitive adhesive sheet can be suitably used for bonding the optical member of the present invention. Note that, although the pressure-sensitive adhesive sheet may have a release liner on the adhesive surface until use, the pressure-sensitive adhesive sheet in the optical member of the present invention does not have a release liner because it is the pressure-sensitive adhesive sheet during use.

[0225] An optical member refers to a member having optical properties (for example, polarization, light refraction, light scattering, light reflection, light transmission, light absorption, light diffraction, optical rotation, visibility, etc.). The substrate constituting the optical member is not particularly limited, but examples thereof include substrates constituting devices (optical devices) such as display devices (image display devices) and input devices, or substrates used in such devices. Examples include polarizing plates, wavelength plates, retardation plates, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflection films, hard-coated films (films in which at least one surface of a plastic film such as a PET film has been hard-coated), transparent conductive films (for example, plastic films having an ITO layer on the surface (preferably, ITO films such as PET-ITO, polycarbonate, and cycloolefin polymer)), design films, decorative films, surface protection plates, prisms, lenses, color filters, transparent substrates (glass sensors, glass display panels (e.g., LCDs), glass substrates such as glass plates with transparent electrodes), and substrates on which these are laminated (these may be collectively referred to as "functional films"). These films may also have a metal nanowire layer, a conductive polymer layer, or the like. These films may also have a mesh of thin metal wires printed on them. The above terms "plate" and "film" respectively include plate-like, film-like, sheet-like, etc. For example, "polarizing film" includes "polarizing plate" and "polarizing sheet", etc. Furthermore, "film" includes film sensors, etc.

[0226] Examples of the display device include a liquid crystal display device, an organic EL (electroluminescence) display device, a PDP (plasma display panel), electronic paper, etc. Examples of the input device include a touch panel, etc.

[0227] The substrate constituting the optical member is not particularly limited, and examples thereof include substrates (e.g., sheet-like, film-like, or plate-like substrates) made of glass, acrylic resin, polycarbonate, polyethylene terephthalate, cycloolefin polymer, metal thin film, etc. As described above, the "optical member" in the present invention also includes members (design films, decorative films, surface protection films, etc.) that play a role in decorating or protecting a display device or input device while maintaining its visibility.

[0228] If the adhesive sheet of the present invention is an adhesive sheet with a substrate and the adhesive sheet constitutes a member having optical properties, the substrate can be considered to be the same as the substrate, and the adhesive sheet can also be said to be an optical member of the present invention.

[0229] When the pressure-sensitive adhesive sheet of the present invention is a pressure-sensitive adhesive sheet with a substrate and the functional film is used as the substrate, the pressure-sensitive adhesive sheet of the present invention can also be used as a "pressure-sensitive adhesive functional film" having the pressure-sensitive adhesive layer on at least one side of the functional film. [Example]

[0230] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples in any way.

[0231] Manufacturing Example 1 <Preparation of acrylic polymer solution 1> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 81.8 parts by mass of butyl acrylate, 5.5 parts by mass of acrylic acid, 12.7 parts by mass of acryloylmorpholine (KJ Chemicals), 0.75 parts by mass of bis{4-[ethyl-(2-acetyloxyethyl)carbamoyl]benzyl trithiocarbonate (Wako Pure Chemical Industries, Ltd.) as a RAFT agent, 0.047 parts by mass of dimethyl 2,2'-azobis(2-methylpropionate) (Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by mass of ethyl acetate as a solvent was stirred at 75°C under a nitrogen atmosphere for 6 hours (RAFT polymerization reaction step 1). This produced acrylic polymer solution 1 containing acrylic polymer P1.

[0232] Example 1 <Preparation of Block Copolymer Solution 2> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 30 parts by weight (solids equivalent) of acrylic polymer solution 1 containing acrylic polymer P1 obtained in Production Example 1, 65 parts by weight of 2-methoxyethyl acrylate, 5 parts by weight of (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide (Wako Pure Chemical Industries, Ltd.) as an ionic monomer, 0.020 parts by weight of 2,2'-azobis(2-methylpropionate)dimethyl (Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by weight of ethyl acetate as a solvent was stirred at 75°C for 6 hours under a nitrogen atmosphere (RAFT polymerization reaction step 2). This produced block copolymer solution 2 containing block copolymer P2. The block copolymer P2 is an ABA triblock copolymer, in which the A segment is an adhesive segment derived from the acrylic polymer P1, and the B segment is a conductive segment containing (2-acryloyloxyethyl)trimethylammonium bis(trifluoromethanesulfonyl)imide as a monomer unit. <Preparation of adhesive composition 1> Pressure-sensitive adhesive composition 1 was prepared by uniformly mixing the following components per 100 parts by mass of block copolymer P2 (base polymer) with block copolymer solution 2 containing block copolymer P2 obtained above. Crosslinking agent: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (trade name "Tetrad C", manufactured by Mitsubishi Gas Chemical Company, Inc.): 0.05 parts by mass <Production of Adhesive Sheet 1> The pressure-sensitive adhesive composition 1 obtained above was applied to a release liner (polyester film, 38 μm thick, manufactured by Mitsubishi Chemical Corporation, MRF#38) with one release surface to form a coating film. This coating film was then dried at 152°C for 3 minutes to form a 25 μm thick pressure-sensitive adhesive layer. A 38 μm thick release liner (polyester film, 38 μm thick, manufactured by Mitsubishi Chemical Corporation, MRF#38) with one polyester film release surface was then bonded to this pressure-sensitive adhesive layer. Thereafter, an aging treatment was performed at 60°C for 1 day to promote a crosslinking reaction in the pressure-sensitive adhesive layer, thereby obtaining pressure-sensitive adhesive sheet 1.

[0233] Example 2 <Preparation of Block Copolymer Solution 3> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 20 parts by weight (solids equivalent) of acrylic polymer solution 1 containing acrylic polymer P1 obtained in Production Example 1, 75 parts by weight of 2-methoxyethyl acrylate, 5 parts by weight of (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide (Wako Pure Chemical Industries, Ltd.) as an ionic monomer, 0.014 parts by weight of 2,2'-azobis(2-methylpropionate)dimethyl (Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by weight of ethyl acetate as a solvent was stirred at 75°C for 6 hours under a nitrogen atmosphere (RAFT polymerization reaction step 2). This produced block copolymer solution 3 containing block copolymer P3. The block copolymer P3 is an ABA triblock copolymer, in which the A segment is an adhesive segment derived from the acrylic polymer P1, and the B segment is a conductive segment containing (2-acryloyloxyethyl)trimethylammonium bis(trifluoromethanesulfonyl)imide as a monomer unit. <Preparation of adhesive composition 2> A pressure-sensitive adhesive composition 2 was prepared in the same manner as in Example 1, except that block copolymer solution 2 was replaced with block copolymer solution 3 containing block copolymer P3 obtained above. <Production of adhesive sheet 2> An adhesive sheet 2 was prepared in the same manner as in Example 1, except that adhesive composition 2 obtained above was used instead of adhesive composition 1.

[0234] Example 3 <Preparation of Block Copolymer Solution 4> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 10 parts by weight (solids equivalent) of acrylic polymer solution 1 containing acrylic polymer P1 obtained in Production Example 1, 85 parts by weight of 2-methoxyethyl acrylate, 5 parts by weight of (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide (Wako Pure Chemical Industries, Ltd.) as an ionic monomer, 0.014 parts by weight of 2,2'-azobis(2-methylpropionate)dimethyl (Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by weight of ethyl acetate as a solvent was stirred at 75°C for 6 hours under a nitrogen atmosphere (RAFT polymerization reaction step 2). This produced block copolymer solution 4 containing block copolymer P4. The block copolymer P4 is an ABA triblock copolymer, in which the A segment is an adhesive segment derived from the acrylic polymer P1, and the B segment is a conductive segment containing (2-acryloyloxyethyl)trimethylammonium bis(trifluoromethanesulfonyl)imide as a monomer unit. <Preparation of adhesive composition 3> A pressure-sensitive adhesive composition 3 was prepared in the same manner as in Example 1, except that block copolymer solution 2 was replaced with block copolymer solution 4 containing block copolymer P4 obtained above. <Production of Adhesive Sheet 3> Adhesive sheet 3 was prepared in the same manner as in Example 1, except that adhesive composition 3 obtained above was used instead of adhesive composition 1.

[0235] Comparative Example 1 <Preparation of Acrylic Polymer Solution 5> In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, a mixture containing 24.5 parts by mass of butyl acrylate, 1.7 parts by mass of acrylic acid, 3.8 parts by mass of acryloylmorpholine (manufactured by KJ Chemicals), 65 parts by mass of 2-methoxyethyl acrylate, 5 parts by mass of (2-acryloyloxyethyl)trimethylammonium bis(trifluoromethanesulfonyl)imide (manufactured by Wako Pure Chemical Industries, Ltd.), 0.25 parts by mass of bis{4-[ethyl-(2-acetyloxyethyl)carbamoyl]benzyl trithiocarbonate (manufactured by Wako Pure Chemical Industries, Ltd.) as a RAFT agent, 0.023 parts by mass of dimethyl 2,2'-azobis(2-methylpropionate) (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by mass of ethyl acetate as a solvent was stirred at 75°C for 6 hours under a nitrogen atmosphere (RAFT polymerization reaction step 1). This resulted in an acrylic polymer solution 5 containing acrylic polymer P5. Acrylic polymer P5 is not a block copolymer, but a conductive polymer containing (2-acryloyloxyethyl)trimethylammonium bis(trifluoromethanesulfonyl)imide as a monomer unit. <Preparation of adhesive composition 4> Pressure-sensitive adhesive composition 4 was prepared in the same manner as in Example 1, except that the block copolymer solution 1 was replaced with the acrylic polymer solution 5 obtained above. <Production of Adhesive Sheet 4> A pressure-sensitive adhesive sheet 4 was prepared in the same manner as in Example 1, except that pressure-sensitive adhesive composition 1 was replaced with pressure-sensitive adhesive composition 4 containing the acrylic polymer P5 obtained above.

[0236] The following evaluations were carried out using the pressure-sensitive adhesive sheets obtained in Examples 1 to 3 and Comparative Example 1. The results are shown in Table 1.

[0237] <Measurement of surface resistance> After peeling off one release liner from each of the pressure-sensitive adhesive sheets obtained in the Examples and Comparative Examples, the surface resistance of the pressure-sensitive adhesive layer was measured using an MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd. in an atmosphere of 23°C and 50% RH.

[0238] <Presence or absence of microphase separation structure> The presence or absence of a microphase-separated structure was confirmed for the pressure-sensitive adhesive layer of each pressure-sensitive adhesive sheet obtained in the Examples and Comparative Examples as follows. First, a sample for observation with a transmission electron microscope (TEM) was prepared. Specifically, the pressure-sensitive adhesive layer was dyed and then rapidly frozen, and a thin section was cut from the pressure-sensitive adhesive layer using an ultramicrotome (manufactured by Leica). The thin section was then observed and photographed using a transmission electron microscope (trade name "HT7820", manufactured by Hitachi High-Technologies Corporation). Next, the obtained TEM image was analyzed and binarized using image analysis software to confirm the presence or absence of phase separation.

[0239] <Evaluation of total light transmittance and haze> One release liner was peeled off from the PSA sheets obtained in Examples 1 to 3 and Comparative Example 1, and the double-sided PSA sheet was attached to a glass slide (manufactured by Matsunami Glass Industry Co., Ltd., "White Polish No. 1," thickness 0.8 to 1.0 mm, total light transmittance 92%, haze 0.2%). The other release liner was then peeled off to prepare a test specimen having a layer structure of double-sided PSA sheet (adhesive layer) / glass slide. The total light transmittance and haze of the test specimen in the visible light region were measured using a haze meter (device name "HM-150N," manufactured by Murakami Color Research Institute Co., Ltd.).

[0240] <Shear storage modulus of adhesive layer> The shear storage modulus of the pressure-sensitive adhesive layer of each of the pressure-sensitive adhesive sheets of Examples 1 to 3 and Comparative Example 1 was examined by dynamic viscoelasticity measurement (first measurement).

[0241] The first measurement sample is prepared as follows: First, for each pressure-sensitive adhesive layer to be measured, 60 pressure-sensitive adhesive layers (25 μm thick) are laminated to obtain a laminated pressure-sensitive adhesive layer (1.5 mm thick). Next, the laminated pressure-sensitive adhesive layer is punched to obtain a cylindrical pellet (1.5 mm thick, 7.9 mm diameter) as the first measurement sample.

[0242] A dynamic viscoelasticity measuring device (product name "ARES", manufactured by Rheometrics) is used for dynamic viscoelasticity measurement. Specifically, a measurement sample is fixed to a 7.9 mm diameter parallel plate jig, and then dynamic viscoelasticity measurement is performed using the device. In this measurement, the measurement mode is shear mode, the measurement temperature range is -70°C to 250°C, the heating rate is 5°C / min, and the frequency is 1 Hz. The shear storage modulus (Pa) of the pressure-sensitive adhesive layer at 25°C is determined.

[0243] [Table 1]

[0244] Although the pressure-sensitive adhesive layers of Examples 1 to 3 and Comparative Example 1 contain the same 5% by weight of ionic monomer, the surface resistance of the pressure-sensitive adhesive layers of Examples 1 to 3 is reduced to less than half that of Comparative Example 1. Therefore, it is thought that the conductive segments of the block copolymer are distributed more unevenly in the continuous phase (sea portion) than in the phase-separated discontinuous phase (island portion) of the pressure-sensitive adhesive layers of Examples 1 to 3, efficiently forming conductive paths.

[0245] Variations of the present invention are listed below. [Appendix 1] A pressure-sensitive adhesive composition containing a block copolymer, The block copolymer comprises an adhesive segment (A) and a conductive segment (B), A pressure-sensitive adhesive composition having a sea-island structure in which the composition is phase-separated into a continuous phase and a discontinuous phase. [Appendix 2] The pressure-sensitive adhesive composition according to Appendix 1, wherein the continuous phase (sea portion) contains the conductive segment (B). [Appendix 3] The pressure-sensitive adhesive composition according to Appendix 1 or 2, wherein the weight ratio of the conductive segment (B) to the adhesive segment (A) (conductive segment (B) / adhesive segment (A)) is 50 / 50 to 99 / 1. [Appendix 4] The pressure-sensitive adhesive composition according to any one of Appendices 1 to 3, wherein the conductive segment (B) contains, as a monomer unit, an ionic compound having a radically polymerizable substituent. [Appendix 5] The pressure-sensitive adhesive composition according to any one of Appendices 1 to 4, wherein the pressure-sensitive adhesive segment (A) contains a radically polymerizable compound as a monomer unit. [Appendix 6] A pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of Appendices 1 to 5. [Appendix 7] Storage modulus at 25°C and 1 Hz is 3 x 10 4 Pa or more 5×10 6 7. The pressure-sensitive adhesive layer according to claim 6, wherein the tensile strength is 0.05 Pa or less. [Appendix 8] The pressure-sensitive adhesive layer according to appendix 6 or 7, which has a total light transmittance (according to JIS K7361-1) of 90% or more. [Appendix 9] The pressure-sensitive adhesive layer according to any one of Appendices 6 to 8, which has a haze (according to JIS K7136) of 3% or less. [Appendix 10] A pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer according to any one of Appendices 6 to 9. [Appendix 11] The adhesive sheet according to appendix 10, having a thickness of 12 to 350 μm. [Explanation of symbols]

[0246] 1 adhesive sheet 10 adhesive layer 11, 12 Release liner

Claims

1. A pressure-sensitive adhesive composition containing a block copolymer, The block copolymer comprises an adhesive segment (A) and a conductive segment (B), A pressure-sensitive adhesive composition having a sea-island structure in which the composition is phase-separated into a continuous phase and a discontinuous phase.

2. The pressure-sensitive adhesive composition according to claim 1 , wherein the continuous phase (sea portion) contains the conductive segment (B).

3. 3. The pressure-sensitive adhesive composition according to claim 1, wherein a weight ratio of the conductive segment (B) to the adhesive segment (A) (conductive segment (B) / adhesive segment (A)) is 50 / 50 to 99 / 1.

4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the conductive segment (B) contains, as a monomer unit, an ionic compound having a radically polymerizable substituent.

5. The pressure-sensitive adhesive composition according to any one of claims 1 to 4, wherein the pressure-sensitive adhesive segment (A) contains a radically polymerizable compound as a monomer unit.

6. A pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of claims 1 to 5.

7. Storage modulus at 25°C and 1 Hz is 3 x 10 4 Pa or more 5×10 6 The pressure-sensitive adhesive layer according to claim 6 , wherein the viscosity is 100 Pa or less.

8. The pressure-sensitive adhesive layer according to claim 6 or 7, which has a total light transmittance (in accordance with JIS K7361-1) of 90% or more.

9. The pressure-sensitive adhesive layer according to any one of claims 6 to 8, having a haze (according to JIS K7136) of 3% or less.

10. A pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer according to any one of claims 6 to 9.

11. The pressure-sensitive adhesive sheet according to claim 10, which has a thickness of 12 to 350 μm.